Paste for solar cell, solar cell, and method for manufacturing same

By using paste containing organic carriers, combined with copper-containing particles, nanoparticles and metal oxide particles, the problems of high cost of silver materials and easy oxidation of copper materials in solar panels are solved, and efficient metallization layer formation and improved stability and efficiency of solar cells are achieved.

CN119560212APending Publication Date: 2025-03-04BERT THIN FILMS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411368629.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-12-12
Filing Date
2020-12-11
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The silver materials used in existing solar panels are costly and difficult to replace, and copper materials are cheap but easily oxidized and diffused, resulting in manufacturing complexity and reduced efficiency.

Method used

A paste containing an organic carrier is used to mix copper particles, nanoparticles and metal oxide particles, and the organic carrier is decomposed and reduced by heating to form an efficient metallization layer.

Benefits of technology

The efficient conductivity of alternative silver materials is achieved, while avoiding the oxidation and diffusion of copper, reducing manufacturing costs and improving the stability and efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560212A_ABST
    Figure CN119560212A_ABST
Patent Text Reader

Abstract

The invention relates to a paste for a solar cell, a solar cell and a manufacturing method thereof. A paste for metallizing a solar cell comprises an organic vehicle and a mixture of copper-containing particles, metal-oxide-containing nanoparticles, and second oxide particles different from the metal-oxide-containing nanoparticles. The second oxide particles include particles of a metal oxide, and the metal of the metal oxide is capable of reducing at least some of the metal-oxide-containing nanoparticles to a metal when heated. The organic vehicle is capable of reducing the metal oxide of the second oxide particles via decomposition of the organic vehicle. The paste comprises a mixture of particles in an organic vehicle, the particles including metallic copper particles, nanoparticles, and metal oxide particles. The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese patent application with an application date of December 11, 2020, application number "202080084323.7", and invention name "Paste for solar cells, solar cells and manufacturing methods thereof".

[0002] Federally Funded Research

[0003] This invention was made with government support from the National Science Foundation under STTR Contract No. I-1448883 and SBIR Contract No. II-1660161 and from the State of Kentucky under STTR Contract No. KSTC-184-512-15-188 and SBIR Contract No. 2018-001.

[0004] CROSS-REFERENCE TO RELATED APPLICATIONS

[0005] This application claims priority to U.S. Application No. 62 / 947,316, filed on December 12, 2019, which is incorporated herein by reference in its entirety. Technical Field

[0006] The present invention generally relates to the manufacture of solar panels and to paste compositions used during the manufacture of components of solar panels, and more specifically to metal-containing pastes, solar cells made with those pastes, and methods of making and using those pastes in the manufacture of solar panels. Background Art

[0007] The solar industry has seen tremendous growth, with average year-on-year growth of about 29% over the past decade. The manufacturing capacity of solar panels reached about 150 GW in 2018. The industry is dominated by crystalline silicon solar cells, with about 95% of the market capacity being crystalline silicon solar panels. However, despite the growth, competitive pricing has led to an 80% drop in the market price of solar panels. As a result, profit margins have narrowed significantly.

[0008] Although solar panels are primarily made of silicon, they have many other structures that convert sunlight into electricity. Solar panels are composed of solar cells that are usually connected in series using tabbing wires / ribbons and sealed between glass front and back panels. Each solar cell includes a silicon wafer that is doped to create a pn junction. When exposed to sunlight, the electric field at the pn junction separates the charge carriers (i.e., electrons and holes). In this way, an electric current is generated.

[0009] Other structures of solar panels can include anti-reflective coatings (e.g., silicon nitride (SiN) and titanium dioxide (TiO2)) on the front or sunlight-exposed side of the doped silicon wafer. The coating reduces light reflection from the cell and thereby increases the efficiency of the cell. The charge carriers generated during light exposure are collected by conductive contacts on the front and back of each cell. The conductive contacts are typically positioned across the front in lines 15 μm to 200 μm wide and spaced every 0.7 mm to 5 mm. Each line can be referred to as a "finger." The spacing and individual widths of the fingers allow sunlight to shine on a large surface area of ​​the doped silicon. The conductive contacts on the back do not need to be transparent. Typically, a thin layer of metal (e.g., aluminum) forms the back of the cell. Additional conductive connections (e.g., busbars 0.1 mm to 2 mm wide and made of silver) are electrically coupled to the fingers and the back aluminum. Although not limited to any particular number, the number of busbars can be from 2 to 8 and can be replaced with other configurations or even non-busbar designs.

[0010] The fingers and busbars on current silicon solar cells are almost all silver (Ag). As demand has increased and reserves have plummeted, manufacturers have minimized the use of silver. This minimization has been achieved by improving the paste formulation and optimizing the paste printing process. One way to reduce costs is to reduce the width of each silver finger. This alone has resulted in a 50% reduction in silver consumption. While further reductions are possible, there is a lower limit below which both device performance and production yields become unacceptable. As manufacturers push the lower limit of silver usage to reduce costs, cheaper silver alternatives are being researched.

[0011] Copper is an ideal replacement for silver. Copper is much cheaper while having similar conductivity. However, one disadvantage is that copper degrades solar cells quickly, so the use of copper complicates manufacturing. To address the degradation problem, especially the diffusion of copper into silicon, different techniques can be used to deposit copper on silicon. One technique is electroplating. While generally successful, electroplating requires newer equipment and increased processing beyond the current silver paste screen printing technology. Since electroplating with copper requires a large capital investment, it has not been adopted by the industry. There are also additional disadvantages.

[0012] Electroplated copper requires a diffusion barrier to be applied on the silicon before the copper is deposited. The copper is then electroplated on this barrier. The diffusion barrier thus separates the copper from the silicon. During use of the solar cell, the barrier prevents the copper from diffusing into the silicon. Another problem is that, unlike silver, copper oxidizes easily.

[0013] Once oxidized, the adhesion and solderability of copper to the diffusion barrier layer are negatively affected. Soldering other electrical connections to the fingers is then problematic. To minimize oxidation, a capping layer of tin or silver is applied over the copper. This complex multi-layer structure requires significant capital expenditures and multiple separate deposition processes. These additional layers and processes offset any material cost advantage of using copper. In addition, the plating baths present environmental, health and safety issues. Ultimately, the material cost savings of using copper are overshadowed by the high capital and production costs.

[0014] To address these and other problems, what is needed in the art is a replacement for silver in solar panels. More particularly, manufacturers seek solutions to the problems associated with using copper instead of silver. Summary of the invention

[0015] The present invention overcomes the above and other shortcomings and disadvantages of solar panels, pastes and methods for making the same. Although the present invention will be described in conjunction with certain embodiments, it should be understood that the present invention is not limited to these embodiments. On the contrary, the present invention includes all substitutions, modifications and equivalents as may be included in the spirit and scope of the present invention.

[0016] According to the principles of the present invention, a paste for metallizing solar cells comprises an organic vehicle, and a mixture of copper-containing particles, metal-oxide-containing nanoparticles, and second oxide particles different from the metal-oxide-containing nanoparticles in the organic vehicle. The second oxide particles include particles of a metal oxide, and when the paste is heated to a temperature at which the organic vehicle decomposes, the metal of the metal oxide is capable of reducing at least some of the metal-oxide-containing nanoparticles to metal.

[0017] In one embodiment, the organic carrier is capable of reducing the metal oxide of the second oxide particles via decomposition of the organic carrier.

[0018] In one embodiment, the organic carrier comprises polyvinyl pyrrolidone.

[0019] In one embodiment, the second oxide particles include glass frit particles.

[0020] In one embodiment, the copper-containing particles include metallic copper particles or copper alloy particles.

[0021] In one embodiment, the metallic copper particles have at least one metal of nickel, cobalt, or manganese on the surface of the metallic copper particles or on the surface of the copper alloy particles.

[0022] In one embodiment, the at least one metal of nickel, cobalt or manganese is in the form of metal particles on the surface of the metallic copper particles or on the surface of the copper alloy particles.

[0023] In one embodiment, the at least one metal of nickel, cobalt or manganese is in the form of metal oxide particles on the surface of the metallic copper particles or on the surface of the copper alloy particles.

[0024] In one embodiment, the metallic copper particles or the copper alloy particles and / or the at least one metal are doped with at least phosphorus.

[0025] In one embodiment, the surfaces of the metallic copper particles or the surfaces of the copper alloy particles are not completely covered by the at least one metal.

[0026] In one embodiment, the at least one metal covers at least a portion of the surface of the metallic copper particles or covers at least a portion of the surface of the copper alloy particles.

[0027] In one embodiment, the metal oxide of the second oxide particles is antimony oxide.

[0028] In one embodiment, the metal-oxide containing nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.

[0029] In one embodiment, the metal-oxide containing nanoparticles include nickel oxide and lead oxide.

[0030] In one embodiment, the metal oxide of the second oxide particles comprises antimony oxide.

[0031] In one embodiment, the metal-oxide containing nanoparticles include nickel oxide, copper oxide, and lead oxide.

[0032] In one embodiment, the paste is free of silver.

[0033] In one embodiment, the ratio of second oxide particles to metal-oxide containing nanoparticles is in the range of 0.50 to 16.96 by weight.

[0034] In one embodiment, the ratio of second oxide particles to metal-oxide containing nanoparticles is in the range of 1.50 to 3.51 by weight.

[0035] In one embodiment, at least one metal of nickel, cobalt and manganese is in the form of metal particles on the surface of the copper-containing particles and the surface area of ​​the copper-containing particles having metal particles is within 1 m 2 / g to 5m2 / g range.

[0036] In one embodiment, at least one metal of nickel, cobalt and manganese is in the form of metal particles on the surface of the copper-containing particles and the surface area of ​​the copper-containing particles having metal particles is within 0.7 m 2 / g to 5m 2 / g range.

[0037] In one embodiment, the copper-containing particles include a mixture of fine copper powder and coarse copper powder.

[0038] In one embodiment, the fine copper powder is characterized by an average particle size ranging from 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size ranging from 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.

[0039] In one embodiment, the organic vehicle is an organic binder and an organic solvent.

[0040] In one embodiment, the organic vehicle further comprises a viscosity modifier.

[0041] In one embodiment, the organic solvent is propylene glycol.

[0042] In one embodiment, the organic vehicle further comprises an organic binder.

[0043] According to the principles of the present invention, the paste comprises an organic vehicle and a mixture of particles in the organic vehicle, the particles comprising metallic copper particles, nanoparticles and metal oxide particles. The nanoparticles comprise at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

[0044] In one embodiment, the metal oxide of the metal oxide particles has a more negative Gibbs free energy of formation than the metal oxide of at least one oxide in the nanoparticles.

[0045] In one embodiment, the metallic copper particles form the largest volume portion of the metal in the paste.

[0046] In one embodiment, the nanoparticles include particles comprising lead oxide.

[0047] In one embodiment, the nanoparticles are nickel oxide and lead oxide.

[0048] In one embodiment, the metal oxide particles comprise particles of antimony oxide.

[0049] In one embodiment, the nanoparticles include particles comprising lead oxide and the metal oxide particles include particles of antimony oxide.

[0050] In one embodiment, the organic vehicle is capable of reducing the metal oxide particles via decomposition of the organic vehicle.

[0051] In one embodiment, the organic carrier comprises polyvinyl pyrrolidone.

[0052] In one embodiment, the metal oxide particles include glass frit particles.

[0053] In one embodiment, the metallic copper particles have at least one metal of nickel, cobalt, or manganese on the surface of the metallic copper particles.

[0054] In one embodiment, the at least one metal of nickel, cobalt or manganese is in the form of metallic particles on the surface of the metallic copper particles.

[0055] In one embodiment, the at least one metal of nickel, cobalt or manganese is in the form of metal oxide particles on the surface of the metallic copper particles.

[0056] In one embodiment, the metallic copper particles and / or the at least one metal are doped with at least phosphorus.

[0057] In one embodiment, the surface of the metallic copper particles is not completely covered by the at least one metal.

[0058] In one embodiment, the at least one metal covers at least a portion of the surface of the metallic copper particles.

[0059] In one embodiment, the metal oxide particles are particles of antimony oxide.

[0060] In one embodiment, the nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.

[0061] In one embodiment, the nanoparticles include nickel oxide and lead oxide.

[0062] In one embodiment, the metal oxide particles are particles of antimony oxide.

[0063] In one embodiment, the nanoparticles include nickel oxide, copper oxide, and lead oxide.

[0064] In one embodiment, the paste is free of silver.

[0065] In one embodiment, the ratio of metal oxide particles to nanoparticles is in the range of 0.5 to 17 by weight.

[0066] In one embodiment, the ratio of metal oxide particles to nanoparticles is in the range of 1.5 to 3.5 by weight.

[0067] In one embodiment, the ratio of metal oxide particles to nanoparticles is in the range of 0.25 to 20 by weight.

[0068] In one embodiment, the ratio of metal oxide particles to nanoparticles ranges from 3 to 17 by weight.

[0069] In one embodiment, the nanoparticles include particles comprising lead oxide and / or lead hydroxide, and the metal oxide particles include particles of antimony oxide.

[0070] In one embodiment, the metallic copper particles are modified to include metal-containing particles on their surfaces.

[0071] In one embodiment, the surface area of ​​the modified metallic copper particles is greater than the surface area of ​​the unmodified metallic copper particles.

[0072] In one embodiment, the surface area of ​​the modified metallic copper particles is between 0.7 m 2 / g to 5m 2 / g range.

[0073] In one embodiment, the surface area of ​​the modified metallic copper particles is 1 m 2 / g to 5m 2 / g range.

[0074] In one embodiment, the metallic copper particles include a mixture of fine copper powder and coarse copper powder.

[0075] In one embodiment, the fine copper powder is characterized by an average particle size ranging from 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size ranging from 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.

[0076] In one embodiment, the organic vehicle is an organic binder and an organic solvent.

[0077] In one embodiment, the organic vehicle further comprises a viscosity modifier.

[0078] In one embodiment, the organic solvent is propylene glycol.

[0079] In one embodiment, the organic vehicle further comprises an organic binder.

[0080] In one embodiment, the organic solvent is one of propylene glycol, dipropylene glycol and tripropylene glycol, or a combination thereof.

[0081] In one embodiment, the metallic copper particles consist of fine copper powder. In one embodiment, the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm.

[0082] According to the principles of the present invention, the paste consists essentially of an organic vehicle and a mixture of metallic copper particles, nanoparticles and metal oxide particles in the organic vehicle. The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

[0083] According to the principles of the present invention, the paste is composed of an organic vehicle and a mixture of metal copper particles, nanoparticles and metal oxide particles in the organic vehicle. The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

[0084] According to the principles of the present invention, a solar cell includes a semiconductor substrate and at least one copper-containing conductor on the semiconductor substrate. The copper-containing conductor includes a plurality of grains of copper or a copper alloy, and at least a portion of a grain boundary between adjacent grains includes at least one of lead, copper, cobalt, manganese, tellurium and bismuth and at least one other metal.

[0085] In one embodiment, the oxide of the at least one other metal has a more negative Gibbs free energy of formation than lead oxide.

[0086] In one embodiment, the at least one other metal is antimony.

[0087] In one embodiment, at least a portion of the grain boundaries further comprise nickel.

[0088] In one embodiment, the copper-containing conductor and the semiconductor substrate meet at an interface, and the interface comprises lead and the at least one other metal between the semiconductor substrate and the grains.

[0089] In one embodiment, the interface comprises a metal silicide.

[0090] In one embodiment, the interface further comprises nickel.

[0091] In one embodiment, the solar cell is free of silver.

[0092] In one embodiment, the copper-containing conductor is a finger.

[0093] In one embodiment, the thickness of the fingers is in the range of 10 μm to 100 μm.

[0094] In one embodiment, the solar cell includes a highly doped silicon emitter layer, and the fingers are in electrical contact with the silicon emitter layer.

[0095] In one embodiment, the resistivity of the fingers is in the range of 2 to 10 times the resistivity of bulk metallic copper.

[0096] In one embodiment, the conductor is a bus bar.

[0097] In one embodiment, the busbar has a thickness in the range of 10 μm to 100 μm.

[0098] In one embodiment, the solar cell includes an anti-reflection layer on the semiconductor substrate, the anti-reflection layer defines an outer surface of the solar cell, and the busbar is in direct contact with the anti-reflection layer but not with the semiconductor substrate.

[0099] In one embodiment, the solar cell further comprises a plurality of bus bars arranged in a pattern wherein the bus bars are spaced apart at a distance less than 40 mm.

[0100] In one embodiment, the solar cell is free of a separately deposited diffusion barrier layer between the copper conductor and the semiconductor substrate.

[0101] According to the principles of the present invention, a method for manufacturing a solar cell includes placing a paste on the surface of a substrate, the paste comprising an organic vehicle and a mixture of particles in the organic vehicle, the particles comprising metallic copper particles, nanoparticles and metal oxide particles. The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide and lead oxide. The paste is heated to a temperature at which the organic vehicle decomposes and at least some of the metal oxides are reduced to metal.

[0102] In one embodiment, heating comprises heating in air.

[0103] In one embodiment, during heating, the metal reduces at least some of the metal-oxide containing nanoparticles to metal.

[0104] In one embodiment, the substrate includes a silicon nitride layer, and during heating, the heated metal oxide and metal react with the silicon nitride layer.

[0105] According to the principles of the present invention, a method for modifying the surface of copper-containing particles for paste includes mixing copper-containing particles with metal ions in a solution, adding a reducing agent to the mixture of copper-containing particles and metal ions to reduce the metal ions to metals so that the metals are deposited on the surfaces of the copper-containing particles, and separating the surface-modified copper-containing particles from the solution.

[0106] In one embodiment, the method further comprises heating the mixture of copper-containing particles, metal ions, and reducing agent.

[0107] In one embodiment, the surface modified copper-containing particles have a surface area greater than the copper particles prior to deposition of the metal.

[0108] In one embodiment, the surface modified copper-containing particles have a surface area of ​​at least 0.66 m 2 / g.

[0109] In one embodiment, the surface modified copper-containing particles have a surface area of ​​at least 0.83 m 2 / g.

[0110] In one embodiment, the metal ion is one or more of nickel, manganese, and cobalt.An embodiment includes a paste comprising surface modified copper-containing particles.

[0111] According to the principles of the present invention, a method of preparing a paste for metallizing solar cells includes mixing together a plurality of particles in an organic vehicle. The plurality of particles includes copper-containing particles, nanoparticles, and second oxide particles.

[0112] In one embodiment, prior to mixing, the method further comprises modifying the surface of the copper-containing particles to increase the surface area of ​​the copper-containing particles by at least 20%.

[0113] In one embodiment, prior to mixing, the method further comprises modifying the surface of the copper-containing particles by exposing the copper-containing particles to a solution and depositing particles of metal and / or metal oxide on the surface of the copper-containing particles.

[0114] In one embodiment, prior to mixing, the method further comprises mixing a first powder comprising the copper-containing particles with a second powder comprising the copper-containing particles, the first powder being characterized by a first average particle size and a first particle size distribution, and the second powder being characterized by a second average particle size and a second particle size distribution, the first average particle size being greater than the second average particle size.

[0115] In one embodiment, all of the copper-containing particles are from a single particle size distribution.

[0116] In one embodiment, mixing includes mixing at least 80 wt % of the copper-containing particles, 1 wt % to 15 wt % of the second oxide particles, and 1 wt % to 10 wt % of the nanoparticles with 1 wt % to 13 wt % of the organic vehicle.

[0117] In one embodiment, mixing includes mixing together metallic copper particles, nanoparticles comprising at least lead, and antimony oxide particles.

[0118] In one embodiment, prior to mixing, the method further comprises modifying the surface of the copper-containing particles to increase the surface area of ​​the copper-containing particles by at least 2%.

[0119] In one embodiment, the copper-containing particles consist of fine copper powder.

[0120] In one embodiment, the fine copper powder is characterized by an average particle size ranging from 1.2 μm to 3.2 μm.

[0121] In one embodiment, the ratio of second oxide particles to metal-oxide containing nanoparticles is in the range of 0.25 to 20 by weight.

[0122] In one embodiment, the ratio of second oxide particles to metal-oxide containing nanoparticles ranges from 3 to 17 by weight. BRIEF DESCRIPTION OF THE DRAWINGS

[0123] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate some embodiments of the present invention and, together with the detailed description given below, serve to explain various aspects of the present invention.

[0124] Figure 1 is a plan view of a cell array of a solar panel according to one embodiment of the present invention.

[0125] Figure 2 According to one embodiment of the present invention Figure 1 An enlarged plan view of one solar cell of the solar panel shown in FIG.

[0126] Figure 3 yes Figure 2 An enlarged perspective cross-sectional view of a solar cell taken along section line 3-3.

[0127] Figure 4 is a schematic diagram of a cross section of a paste line on a substrate according to one embodiment of the present invention.

[0128] Figure 5 According to one embodiment of the present invention Figure 4Schematic diagram of a cross section of a paste line after drying.

[0129] Figure 6 is Figure 5 Schematic diagram of the cross section of the wire after wire firing.

[0130] Fig. 7A and Figure 7B is a flow chart for making exemplary nanoparticles according to an embodiment of the present invention.

[0131] Figure 8 Shown is a TEM image with overlaid elemental analysis of particles made according to one embodiment of the present invention.

[0132] Fig. 9A is a flow chart for surface modification of copper-containing particles prior to use in a paste according to one embodiment of the present invention.

[0133] Fig. 9B is a flow chart for paste formulation according to one embodiment of the present invention.

[0134] Fig.10 is a graph showing a temperature profile of a reaction mixture according to an exemplary process for surface modification of copper-containing particles according to one embodiment.

[0135] Fig.11A , Fig. 11B , Fig. 11C and Fig.11D are the normalized short-circuit current density (J) of the paste prepared without modifying the surface of the copper-containing particles. sc ), normalized open circuit voltage (V oc ), normalized fill factor (FF) and normalized efficiency (η) accelerated aging test graphs.

[0136] Fig. 12A is the normalized open circuit voltage (V) of the pastes made using different embodiments of the nanoparticles and fired at different temperatures. oc ) accelerated aging test diagram.

[0137] Fig. 12B , Fig. 12C , Fig.12D and Fig.12E is a graph of the effects of accelerated aging testing on the PV performance of pastes made using different embodiments of nanoparticles and fired at different temperatures.

[0138] Fig.12F and Figure 12G is the normalized open circuit voltage (V) of the pastes made using different embodiments of the nanoparticles and fired at different temperatures. oc) and normalized short-circuit current density (J sc ) accelerated aging test diagram.

[0139] Fig.12H and Fig.12I is an accelerated aging test graph of normalized fill factor (FF) and normalized efficiency (η) of pastes made using different embodiments of nanoparticles and fired at different temperatures.

[0140] Fig.13A , Fig. 13B , Fig. 13C and Fig.13D is the normalized short-circuit current density (J) of exemplary embodiments of the paste on cells from different manufacturers. sc ), normalized fill factor (FF), normalized open circuit voltage (V oc ) and normalized efficiency (η).

[0141] Fig.13E , Fig.13F , Figure 13G and Fig.13H is a current-voltage graph after accelerated aging testing of exemplary embodiments of the paste on batteries from different manufacturers.

[0142] Fig.14A , Fig. 14B and Fig. 14C is a current versus voltage graph for accelerated aging of exemplary cells made from pastes containing increasing amounts of the second oxide and nanoparticles.

[0143] Fig.15A , Fig. 15B , Fig. 15C , Fig.15D and Fig.15E and are respectively the normalized short circuit current density (J) of different embodiments of the paste containing an increased ratio of the second oxide to the nanoparticles. sc ), normalized open circuit voltage (V oc ), normalized fill factor (FF), normalized efficiency (η) and normalized resistance accelerated aging test graphs. Fig.15F is an accelerated aging test graph of normalized FF as the second oxide in the paste varies relative to the nanoparticles.

[0144] Fig.16A , Fig. 16B , Fig. 16C , Fig.16D and Fig.16E and the normalized short-circuit current density (J) of the exemplary embodiment using the paste containing copper particles with increased surface modification amount, respectively. sc ), normalized open circuit voltage (V oc), normalized fill factor (FF), normalized efficiency (η) and normalized resistance accelerated aging test graphs.

[0145] Fig.17A , Fig. 17B , Fig. 17C and Fig.17D is a graph of current density versus voltage for exemplary cells made from different pastes using copper-containing particles with increasing amounts of surface modification after accelerated aging testing.

[0146] Fig.18A , Fig.18B and Fig. 18C is a graph showing the effect of varying the ratio of two copper-containing particles comprising different particle size ranges on the surface area, volume, and weight contribution of the total copper loading in the paste when the total surface area contribution of the copper-containing particles remains constant.

[0147] Fig.18D and Fig.18E Optical microscope images of pastes using 100% coarse (10 μm to 22 μm) copper particles and 100% fine (1.2 μm to 3.2 μm) copper particles, respectively.

[0148] Fig.19A and Fig.19B is a graph illustrating the effect of the ratio of coarse copper-containing particles to fine copper-containing particles in the paste on the resistivity of the contact formed after firing.

[0149] Fig. 20A and Fig. 20B is a graph showing current density versus voltage for paste embodiments using different ratios of coarse copper-containing particles to fine copper-containing particles.

[0150] Fig. 20C is a graph of spindle speed versus viscosity for two exemplary pastes made using surface-modified copper-containing particles having different particle shapes.

[0151] Fig.20D and Fig.20E are cross-sectional SEM micrographs of exemplary pastes made using surface-modified copper-containing powders with different particle shapes after firing.

[0152] Fig.21A , Fig. 21B and Fig. 21C Optical images of pastes made by changing the ratio of coarse copper-containing particles to fine copper-containing particles from 100:0, 90:10, and 80:30 after firing, respectively.

[0153] Fig. 22 are cross-sectional SEM images of fingers made from the pastes of various embodiments after firing.

[0154] Fig.23 is an x-ray diffraction pattern of a deposited and heat-treated film made using nanoparticles according to an embodiment of the present invention.

[0155] Fig.24A and Fig. 24B is a graph of current density versus voltage showing the effect of increasing the amount of organic vehicle and varying the firing temperature on the electrical characteristics of the cell in some embodiments of the paste.

[0156] Fig.25A , Fig.25B , Fig.25C , Fig.25D , Fig.25E and Fig.25F They are the bulk resistivity, contact resistivity, and J of the second oxide and nanoparticles. sc , FF, V oc Design of experiment (DOE) influence diagram for the interaction of and η.

[0157] Fig.26A and Fig.26B ] and are SEM images showing the microstructure formed after firing a paste containing a high proportion of the second oxide, respectively.

[0158] Fig.27A , Fig.27B and Fig.27C are cross-sectional SEM images of fingers printed with exemplary pastes containing different ratios of coarse-sized copper-containing powder, medium-sized copper-containing powder, small-sized copper-containing powder, and fine-sized copper-containing powder.

[0159] Fig.28A and Fig.28B Optical images of the front and back sides, respectively, of prints made with an exemplary paste formulated to have low porosity.

[0160] Fig.29A , Fig.29B , Fig.29C , Fig.29D and Fig.29E is a graph of voltage versus current density for pastes containing increasing amounts of the second oxide.

[0161] Fig. 30A , Fig. 30B , Fig. 30C , Fig.30D and Fig.30E is the normalized short-circuit current density (J) of the exemplary paste with increasing firing duration sc ), normalized fill factor (FF), open circuit voltage (V oc ), normalized efficiency (η) and accelerated aging test graphs of normalized resistance.

[0162] Fig.30F , Figure 30G and Fig. 30H is a graph of current density versus voltage for accelerated aging tests of exemplary pastes with increasing firing durations.

[0163] Fig.31A , Fig.31B , Fig.31C , Fig.31D , Fig.31E The surface area of ​​the surface-modified fine copper-containing particles in the paste is 1.10 m 2 / g, the amount of organic carrier in the paste and the firing conditions (i.e., holding time) have an effect on J sc 、V oc , FF, η and the influence of the resistance on the entire finger.

[0164] Fig.31F , Figure 31G , Fig.31H , Fig.31I , Fig.31J The surface area of ​​the surface-modified fine copper-containing particles in the paste is 2.65 m 2 / g, the amount of organic carrier in the paste and the firing conditions (i.e., holding time) have an effect on J sc 、V oc , FF, η and the influence of the resistance on the entire finger.

[0165] Figure 31K , Figure 31L , Figure 31M , Fig.31N , Fig.31O The surface area of ​​the surface-modified fine copper-containing particles in the paste is 2.65 m 2 / g, the amount of organic carrier in the paste and the firing conditions (i.e., holding time) have an effect on J sc 、V oc , FF, η and the influence of the resistance on the entire finger.

[0166] Fig.32A , Fig.32B , Fig.32C , Fig.32D , Fig.32E and Fig.32F is an optical microscope image of the finger after firing, where Fig.32A No nanoparticles, Fig.32B The second oxide to nanoparticle ratio is 16.75, Fig.32C The ratio of the second oxide to the nanoparticles is 8.37, Fig.32D The second oxide to nanoparticle ratio is 5.58, Fig.32EThe second oxide to nanoparticle ratio is 4.19, Fig.32F The second oxide to nanoparticle ratio is 3.35.

[0167] Fig.33A and Fig.33B The effect of increasing the amount of glass frit in the paste on the PV performance (fill factor, FF) is shown as the use surface area contribution is (a) about 0.80 m 2 / g paste and (b)0.57m 2 / g of paste as a function of the print weight of the paste made with copper-containing powder.

[0168] Fig.34A , Fig.34B , Fig.34C and Fig.34D The PV performance is shown (respectively Fig.34A Short circuit current density, Fig.34B Open circuit voltage, Fig.34C Fill factor and Fig.34D Efficiency) as a function of belt speed for firing cells in an industrial IR belt furnace.

[0169] Fig.35 Current-voltage (IV) curves under dark and light conditions are shown for a paste made using only fine 1.2 μm to 3.2 μm copper-containing powder.

[0170] Fig.36A , Fig.36B and Fig.36C The effect of using copper-containing particles with the following surface areas on the open circuit voltage V oc Impact: Fig.36A 0.51m 2 / g paste, Fig.36B 0.57m 2 / g paste, Fig.36C 0.65m 2 / g paste.

[0171] Fig.37A and Fig.37B The effect of accelerated aging test at 200°C on PV performance (using CuBert TM Multicrystalline Si cells with full Al BSF back contacts metallized by paste Fig.37A Open circuit voltage and Fig.37B pseudo fill factor).

[0172] Fig.38A and Fig.38BThe efficiency of monocrystalline silicon PERC solar cells printed with pastes made using standard Ni / Ni / Pb nanoparticles with a Ni / Pb ratio of 1.52 and a ratio of 0.52 is shown, and the effect of doubling the ratio of nanoparticles and the amount of binder on the PV performance is also shown.

[0173] Fig.39A , Fig.39B and Fig.39C The effects of firing conditions on the use of a 2.05 wt % binder in FIG39A, a 2.35 wt % binder in FIG39B, and Fig.39C Effect of 2.64 wt% binder paste printing on the resistance of 22 fingers with a length of 3.2 mm.

[0174] Fig.40 is an optical micrograph of a finger according to one example.

[0175] Fig.41A and Fig.41B are optical microscope images of fingers printed with two different screen sizes before firing according to one example. DETAILED DESCRIPTION

[0176] Reference Figure 1 and Figure 2 , the solar panel (not shown) includes a plurality of solar cells 12. Figure 1 Not shown, the cell array 10 can be a component package including a front plate, a back plate, and a sealant layer (e.g., ethylene vinyl acetate). A silicon substrate is located between the front plate and the back plate between the sealant layers. Interconnectors are required to electrically connect the cells 12 within the array 10 together. These components may be enclosed in a frame (not shown). The number of cells 12 within the array 10 can be different than that shown. For example, a solar panel may include sixty or more cells. Other common cell counts are 72 and 90. However, embodiments of the present invention are not limited to any number of solar cells 12 in the cell array 10.

[0177] As described herein, one or more of the cells 12 may include one or more electrical conductors (i.e., electrodes) containing copper. The largest proportion of the metal conductor may be copper, with the remaining proportion being other metals and / or metal-containing materials. In one embodiment, one or more of the solar cells 12 are free of silver. Advantageously, the solar cells 12 can be produced in a cost-effective manner because the copper-containing conductor replaces the silver conductor. In addition, as described herein, the copper-containing conductor is produced from a copper-containing paste during the metallization process. As another advantage, the paste of the present invention can be substituted for processes currently using silver-containing pastes, such as solar cell / panel manufacturing processes. As will be appreciated, this eliminates the necessity for large capital investments observed using copper electroplating techniques while providing a cost-effective method for producing solar cells having primarily copper electrodes and in which silver is not present.

[0178] Reference Figure 2 and Figure 3 , solar cell 12 includes a semiconductor substrate or wafer 14. Wafer 14 is single crystal silicon. However, embodiments of the present invention are equally applicable to multicrystalline silicon substrates and other semiconductor substrates and films. Figure 3 , the wafer 14 may include an n-type doped silicon region 16 adjacent to a p-type doped silicon region 18 to form a pn junction. Other architectures may include an inversion of p- and n-doped regions and a combination of locally doped regions. The combination of region 16 and region 18 allows electrons to separate from holes when the silicon is struck by a photon of light. An anti-reflective coating 20 covers the n-type doped silicon region 16 and defines a front surface 22 of the solar cell 12. For example, the anti-reflective coating 20 may be silicon nitride (SiN). The anti-reflective coating 20 reduces incident light (caused by Figure 3 The anti-reflective coating 20 also helps to passivate the surface of the silicon wafer 14, which reduces recombination losses. This improves the electrical efficiency of the solar cell 12.

[0179] A plurality of electrical conductors 26, referred to as fingers, are exposed at the front surface 22 of the solar cell 12. Figure 3As shown, the fingers 26 penetrate the anti-reflective coating 20 and are in electrical contact with the wafer 14, in particular, with the n-type doped silicon region 16. The back conductor 30 is in electrical contact with the p-type doped region 18 of the wafer 14 opposite to the fingers 26. The conductors 26 and 30 conduct the current generated by the photons of light that strike the wafer 14 to ultimately generate electricity. According to an embodiment of the present invention, one or more of the fingers 26 and / or the back conductor 30 can be copper-containing, and in this regard can also be silver-free. The fingers 26 manufactured as described herein have an electrical conductivity that is 2 to 10 times less conductive than bulk metallic copper. The resistivity of the fingers is the inverse of their electrical conductivity. The back conductor 30 can be formed of aluminum or another electrical conductor, and its thickness is in the range of 10 μm to 100 μm. As described above, for example, the fingers 26 can be formed of a copper-containing paste and thus replace the silver-containing paste in the manufacture of the solar cell 12.

[0180] In this regard and now with reference to Figure 4 , Figure 5 and Figure 6 According to one embodiment of the present invention, the copper-containing paste 32 (shown in Figure 4 ) is placed on the front surface 22 of the substrate 40. The copper-containing paste 32 can be screen printed on the substrate 40 or dispensed by another method. As shown, the substrate 40 includes the anti-reflective coating 20 and the wafer 14. In the case where the back conductor 30 is made of aluminum, it can already exist (as shown) or can be formed during the process of producing the fingers 26. During manufacturing, the substrate 40, the anti-reflective coating 20, the wafer 14, the back conductor 30 and the paste 32 are used or deposited to produce Figure 2 The battery 12 is shown.

[0181] During printing on substrate 40, reference is made to Figure 4 , the copper-containing paste 32 defines an elongated body (e.g., a line) having a height, a width, and a length on the substrate 40. As described below, the elongated body is transformed into a finger during firing of the paste 32. To this end, the paste 32 includes a plurality of particles 42 contained in an organic vehicle 44. The rheological properties of the paste 32 can be adjusted by changing the composition of the organic vehicle 44 and / or the particles 42 to allow the paste 32 to be dispensed by a screen printing process (e.g., a process similar to that used to screen print a silver-containing paste on a silicon wafer) or by another method. The rheological properties of the paste 32 are sufficient to allow the paste 32 to be dispensed while also allowing the paste 32 to maintain the dispensed pattern and not spread across the substrate 40; thereby allowing the fingers to maintain a high aspect ratio (finger height / finger width).

[0182] By way of example only and not limitation, the organic carrier 44 can be a mixture of an organic binder and one or more solvents, dispersants, viscosity modifiers, and / or surface tension modifiers. Exemplary binders include polyvinyl pyrrolidone (PVP), ethyl cellulose, and monosaccharides such as fructose. In addition to water, exemplary solvents include alcohols, ester alcohols, and glycols, such as propylene glycol, ethylene glycol, polyethylene glycol, Texanol TM Ester alcohols, as well as ether alcohols and glycols, such as diethylene glycol and triethylene glycol. Exemplary viscosity and surface tension modifiers include 111. 180, 190, RE-610 and sodium stearate, to name a few. The volume of organic vehicle 44 and the proportion of each type of particles 42 in the paste 32 can be adjusted to meet the desired rheological (e.g., viscosity) specifications. Typically, the paste 32 can include only a few weight percent of the organic vehicle 44. For example, the paste 32 includes an organic vehicle 44 in a range from 1 wt % to 15 wt %.

[0183] The copper-containing paste 32 is a mixture of particles of different compositions. That is, the paste 32 may be a mixture of powders that provide all of the particles 42. Each powder may include particles 42 having different compositions, particle sizes, and / or particle shapes.

[0184] In one embodiment, the copper-containing paste 32 includes a plurality of copper-containing particles 46 that form the largest volume portion of the particles 42 in the paste 32. The copper-containing particles 46 can form the majority of the volume of the fingers 26. After firing, by virtue of the composition of the particles 42, the fingers 26 can provide sufficient conductivity to promote effective solar cell performance through metallic copper or copper-containing metal. For example, the copper-containing particles 46 can be metallic copper and form 48% to 88% of the solids in the paste 32 by volume. This can be converted to at least 80% by weight of copper metal in the paste 32 before drying. The range of copper metal in the paste 32 can be 62% to 98% by weight. Although the copper-containing particles 46 are described with reference to metallic copper, the copper-containing particles 46 are not limited to metallic copper, which can contain small amounts of impurity elements. The copper-containing particles 46 can be copper-containing alloy particles or copper-containing non-metallic (e.g., oxide) particles that can be reduced to copper or copper-containing alloys. Copper-containing alloys are alloys containing copper as their main component, such as bronze (copper-tin alloy) and brass (copper-zinc alloy). As another example, copper alloys may include copper in combination with other metallic elements including nickel, aluminum, and / or lead. Copper-phosphorus alloys are also contemplated. Copper-containing particles 46 may be a mixture of two or more of metallic copper, copper-containing alloys, and non-metallic copper-containing materials.

[0185] The copper-containing particles 46 are provided in the paste 32 by a powder described by a particle size distribution. For example, a particle size distribution of a copper powder may include particles with a size in the range of 10 μm to 22 μm. That is, the powder contains particles with an average particle size within the range from 10 μm to 22 μm. By further example, a narrower particle size distribution of the copper-containing particles 46 includes particles with a size range of 10 μm to 20 μm. Other exemplary examples include a gradually narrower particle size distribution: particles with a size range of 7.5 μm to 14.7 μm (these are D, D, and D, respectively). 10 and D 90 ), 1.8μm to 7.7μm (these are D 10 and D 90 ), 1.2μm to 3.2μm (these are D 10 and D 90 ), or 0.2 μm to 1.6 μm (these are D 10 and D 90 ) range. Copper-containing particles 46 can be particles from one powder having a particle size distribution (e.g., one of the exemplary distributions above), or a mixture of multiple different powders such that multiple different particle size distributions are mixed in paste 32. Particle size distribution is related to the surface area per unit weight of powder. Therefore, as the particle size distribution moves toward smaller particles, the surface area per gram of powder increases.

[0186] For example, a powder of coarse copper-containing particles 46 can be mixed with a powder of fine copper-containing particles 46. The fine copper-containing powder 46 can be filled in the gaps between the larger copper-containing particles 46 in the paste 32. This results in a bimodal particle size distribution of the copper-containing particles 46 in the paste 32 and can maximize the volume of copper in the paste 32. In this way, any combination of two or more of the particle size distributions confirmed above can be mixed together to adjust the volume percentage of copper in the paste 32 to a desired range. For a binary mixture, the ratio of copper-containing powders of different sizes can be in the range of 60 wt % coarse-40 wt % fine to 90 wt % coarse-10 wt % fine by weight. For example, a coarse copper powder with a particle size distribution in the range of 10 μm to 20 μm can be mixed with a fine copper powder with a particle size distribution in the range of 1.2 μm to 3.2 μm at a ratio of 90 wt % coarse to 10 wt % fine. Other ratios of two or more copper powders are possible, for example, a coarse copper powder having a particle size distribution in the range of 7.5 μm to 14.7 μm can be mixed with a fine copper powder having a particle size distribution in the range of 1.2 μm to 3.2 μm at a ratio of 70% coarse to 30% fine by weight. As an example of four different copper-containing powders, a particle size distribution in the range of 10 μm to 22 μm is mixed with three other copper-containing powders having a particle size distribution in the range of 7.5 μm to 14.7 μm, 1.8 μm to 7.7 μm, and 1.2 μm to 3.2 μm, respectively, in a weight ratio of 37 to 21 to 12 to 30. Copper-containing powders according to embodiments of the present invention can be purchased from Bean Town (copper flakes), Chemical Store (commodity Cu112SP), ACuInternational (commodity 610 and 603), and Ames Goldsmith (commodity C1-2000).

[0187] It should be understood that Figure 4 32 is a schematic diagram of a copper-containing paste 32. Although particles 42 within paste 32 are shown as spherical morphologies, embodiments of the present invention are not limited to any individual particle in the particles being spherical. Other particle morphologies are possible, namely, flake-like, needle-like, multifaceted, dendritic, spongy, round, porous, elliptical, linear, and decorative, to name a few.

[0188] Reference Figure 4, the paste 32 includes other particles 42 that are at least different in composition from the copper-containing particles 46. In an exemplary embodiment, the other particles 42 in the paste 32 include nanoparticles 50. Each of the nanoparticles 50 is a discrete object, wherein all three dimensions are equal to or less than 100 nm. The nanoparticles 50 can form agglomerates or aggregates, in which case the agglomerates or aggregates can measure up to 1 μm in each orthogonal direction. In one embodiment, the nanoparticles 50 are metals, metal oxides, and / or metal hydroxides of one or more of nickel (Ni), copper (Cu), lead (Pb), cobalt (Co), manganese (Mn), and silver (Ag). By way of example only, the mixed elemental nanoparticles can include Cu, Ni, and Pb; Ni, Ni, and Pb; or Mn, Mn, and Pb. For example, the nanoparticles 50 include nanoparticles of mixed oxides of Cu / Ni / Pb, Cu-Ag / Ni / Pb nanoparticles, mixed oxides of Co / Co / Pb nanoparticles, mixed oxides of Ni-Co / Ni / Pb nanoparticles, mixed oxides of Ni-Ag / Ni / Pb nanoparticles, and mixed oxides of Mn / Mn / Pb nanoparticles. As described below, each metal in the A / B / C notation (e.g., Cu / Ni / Pb) can be provided by a metal salt to synthesize Ni / Ni / Pb nanoparticles, wherein Ni is provided by two different nickel-containing salts. Those metals can be oxidized during synthesis. The nanoparticles 50 may be doped with one or more of phosphorus (P), chloride (Cl), and boron (B), which may be due to the process of synthesizing the nanoparticles 50. Referring to FIG. Fig. 7A and Figure 7B An exemplary process for making nanoparticles 50 is described.

[0189] The nanoparticles 50 are included in the paste 32 in an amount sufficient to reduce or eliminate oxidation of metallic copper or copper alloys in the paste 32 or formed during the manufacture of the solar cell 12, as further described below, while also reducing diffusion of copper into the wafer 14 during use of the solar cell 12. The nanoparticles 50 also enable etching of the anti-reflective coating 20 and allow electrical connection of the copper to the wafer 14. The reduction in copper diffusion can be achieved by forming a barrier layer between the copper of the fingers 26 and the wafer 14 during manufacture. Without being bound by any theory, it is believed that the nanoparticles 50 participate in the formation of the barrier layer so that the elements of the nanoparticles 50 form an interface between the silicon of the wafer 14 and the copper from the copper-containing particles 46. For example, the nanoparticles 50 can be present in the paste 32 in an amount up to 17 weight percent. As another example, the nanoparticles 50 can be present in the paste 32 in a detectable amount of up to 5% by weight; up to a detectable amount of 3% by weight; about 0.2% by weight (or close to the lower limit of detection) to up to 3% by weight; or about 0.2% by weight to up to 5% by weight. Mixtures of different nanoparticles are also contemplated, where the total weight of the mixture falls within the above ranges. For example, the mixture of nanoparticles 50 can be 50% by weight Ni / Ni / Pb nanoparticles and 50% by weight Cu / Ni / Pb nanoparticles.

[0190] like Figure 4 and Figure 5 As shown, the copper-containing particles 46 can be surface-modified. In one embodiment, the particles 46 are coated with smaller particles 56, which surround at least a portion of each individual copper-containing particle 46. The copper-containing particles 46 are substantially coated with smaller particles 56. The particles 56 can cover the entirety of each particle 46. However, the particles 56 can only cover a small portion of each surface of the particles 46, so the particles 56 can be unevenly distributed on the surface of each particle 46. In this arrangement, the uncovered areas of the particles 46 are exposed in the paste 32. This configuration of smaller particles covering larger particles produces an increase in surface area measured from the surface area of ​​the uncoated particles 46 to the surface area of ​​the copper particles 46 coated with the particles 56. The surface area can be increased by up to 20%. For example, a surface area of ​​0.6 m 2 The uncoated copper particles of 0.83 m / g can be modified to have a surface area of ​​at least 0.83 m 2 As another example, the copper-containing particles 46 may be modified to have a surface area of ​​0.83 m 2 / g to 1.61m 2 / g range. In one embodiment, the surface area increase is 1.5%. Thus, as an example, the surface area increase ranges from 1.5% to 20%. However, the surface modification can also produce a surface area increase of up to 3,000% over the surface area of ​​the uncoated particle 46. The surface area can be measured by the BET method. Using The surface area was measured using a Gemini VII Series 2390 Surface Area Analyzer. Degassing was performed in a FlowPrep060 system at 160°C for 2 hours under an inert gas (nitrogen, N2) flow. The degassing process desorbs contaminants such as water from the powder surface, and the gas removes it from the sample tube. The Gemini unit uses N2 physical adsorption to measure the adsorption isotherm of the powder. Multi-point measurements of the isotherm are used to calculate the surface area of ​​the powder using the Brunauer-Emmett-Teller equation. Controlling the surface area of ​​the copper-containing particles 46 can control the formation of the interface between the fingers 26 and the wafer 14.

[0191] according to Fig. 9A In the process shown, the copper-containing particles 46 can be coated with particles 56. The particles 56 can be metal or oxides / hydroxides of various metals. For example, the particles 56 can be metal copper and / or oxides / hydroxides of at least one of copper (Cu), nickel (Ni) and manganese (Mn). The particles 56 may be doped with phosphorus (P) due to the process of synthesizing it, as described below. The particles 56 can nucleate and grow on the surface of the copper-containing particles 46. Therefore, the particles 56 can be at least weakly bonded to the surface of each copper-containing particle 46. The embodiments of the present invention are not limited to the bonding between the particles 56 and any other particles in the paste 32. The particles 56 located at the surface are positioned to protect the copper-containing particles 46 from oxidation or other undesirable reactions during manufacturing. The composition of the particles 56 can form at least a portion of the interface between the fingers 26 and the wafer 14.

[0192] Continue to refer to Figure 4, the paste 32 includes second oxide particles 52. Similar to particles 56, second oxide particles 52 can also participate in reducing or inhibiting oxidation of copper in copper-containing particles 46, while enabling etching of anti-reflective coating 20. Therefore, second oxide particles 52 make it possible to make electrical connections between copper of fingers 26 and wafer 14 during manufacturing, as described below. In addition or as an alternative, second oxide particles 52 can help form an interface between copper in fingers 26 and silicon in wafer 14 to prevent diffusion of copper into silicon during use of solar cell 12. Second oxide particles 52 can be reduced to their constituent metals during heating, and then can be able to reduce at least oxide / hydroxide nanoparticles 50 and / or oxide / hydroxide of particles 56. In addition, second oxide particles 52 alone or in combination with one or both of nanoparticles 50 and particles 56 can form a liquid sintering aid during the manufacture of solar cell 12. Liquid phase sintering is a technique for sintering alloys and composite materials. In a composite material containing two materials, the second material will have a lower melting point than the first material. Thus, one material will melt at a given processing temperature while the other remains solid. When the primary material is soluble in the liquid phase, the liquid will wet the particles and create capillary forces that hold the particles together in a tightly packed structure. In addition, the liquid is able to achieve a higher diffusion rate, which contributes to faster sintering and lower processing temperatures. The ratio of nanoparticles 50 to second oxide particles 52 to particles 56 in the paste 32 can at least partially control the etching process between the paste 32 and the anti-reflective coating 20 during firing.

[0193] With respect to the oxides in the reducing paste 32, the second oxide particles 52 may be one or more metal oxides having a more negative Gibbs free energy of formation than at least one of the oxides of the nanoparticles 50 and the oxides of the particles 56. For example, the second oxide particles 52 may have a more negative Gibbs free energy of formation than at least one of copper oxide (Cu2O, CuO), lead oxide (PbO, PbO2), or nickel oxide (NiO) at the temperature at which the wafer 14 and the paste 32 are heated during manufacturing. In one embodiment, the second oxide particles 52 are antimony oxide (Sb2O3) particles. Other second oxide particles 52 include, but are not limited to, tin oxide (SnO, SnO2), tellurium oxide (TeO), manganese oxide (MnO, MnO2), phosphorus oxide (P4O 10, PO2), bismuth oxide (Bi2O3), chromium oxide (Cr2O3), and aluminum oxide (Al2O3). These oxides can be used to reduce other oxides in the paste 32 according to the oxidation state of the second oxide particles 52, the melting point temperature of the second oxide particles 52, the processing temperature and partial pressure of the reducing environment surrounding the second oxide particles 52. In addition, the second oxide particles 52 may include glass frit particles, such as lead silicate glass or other metal-containing glass, which contains one or more oxide components having a more negative Gibbs free energy of formation than at least one of Cu2O, CuO, PbO2, PbO and NiO. Exemplary glass frit particles include borate glass, such as B2O3-PbO-ZnO glass, and silicate glass, such as PbO-SiO2-B2O3-Al2O3 glass.

[0194] The paste 32 may include 1 wt % to 15 wt % of the second oxide particles 52. The surface area of ​​the second oxide particles 52 may be 2 m 2 / g to 2.5m 2 / g range. The ratio of the second oxide particles 52 to the nanoparticles 50 can determine the amount of oxide reduced during heating and / or the amount of sintering aid formed. In one embodiment, the ratio of the second oxide particles 52 to the nanoparticles 50 is in the range of 0.50 to 16.96 by weight. In another embodiment, the ratio of the second oxide particles 52 to the metal-oxide-containing nanoparticles is in the range of 1.50 to 3.51 by weight. As used herein, "essentially consisting of..." means that no other elements or particles are intentionally added to the paste. However, the impurity content of other elements in the form of oxides or metals from the powder or manufacturing process is taken into account.

[0195] Reference Figure 4 and Figure 5 Once the paste 32 is dispensed, the substrate 40 and the paste 32 are exposed to a temperature of 20°C to 400°C, or more specifically 20°C to 200°C, to dry. During drying, at least some of the organic vehicle 44 is removed from the paste 32. This Figure 5 This is schematically indicated by arrow 54 .

[0196] After drying, the particles 42 of the paste 32 are fired in the metallization process to produce the fingers 26 and / or the back conductor 30. In one embodiment, the manufacture of the solar cell 12 (including drying and firing) is completed in air. That is, the atmosphere during drying and firing is not controlled or changed by adding inert gases or reducing gases. During firing, the particles 42 are exposed to a temperature of 600° C. to 930° C. in air for 0.8 seconds to 10 seconds, depending on the temperature profile of the furnace, the belt speed, and the composition of the paste 32. At these temperatures and times, in one embodiment, at least one organic binder remaining from the organic vehicle 44 decomposes and forms a reducing environment located around the particles 42. It is believed that this environment reduces the second oxide particles 52. The reduction of at least some of the second oxide particles 52 produces at least one metal from the second oxide particles 52. For example, it is believed that the composition of the organic vehicle 44 reduces antimony oxide (Sb2O3) to metallic antimony (Sb). As another example, the organic vehicle 44 can also reduce lead oxide to lead (Pb).

[0197] In turn, the metal from the second oxide particles 52 reduces at least some of the nanoparticles 50 and / or particles 56 on the copper-containing particles 46. Continuing with the example of Sb, the generated metallic Sb reduces the oxides of the nanoparticles 50 and the oxides of the particles 56. In the presence of PbO, the metallic Sb can be reduced by PbO to generate Pb, and Pb can contribute to the reduction of the copper oxide. Therefore, by the characteristics of the particles 42 in the paste 32, a cascade-type reduction reaction can be promoted by the decomposition of the organic vehicle 44. In this cascade reduction, one oxide is reduced to a metal. The metal then reduces another oxide in the mixture of particles 42. Depending on the temperature; the composition and volume of the nanoparticles 50, the second oxide particles 52, and the particles 56; and the proportion of the organic vehicle 44 in the paste 32, the cascade reduction reaction can reduce all oxides in the paste 32 to their constituent metals. This can include any copper oxides present in the paste 32. In this case, the paste containing a majority of metal oxides contains a composite of different metals.

[0198] At the temperatures to which the particles 42 are exposed during firing, the reduced nanoparticles 50 and second oxide particles 52 can form a liquid sintering aid and can reduce and / or coat the copper-containing particles 46. Metal from the nanoparticles 50 and second oxide particles 52 can react with the antireflective coating 20. This combination of particles is believed to produce an etchant.

[0199] like Figure 5 and Figure 6 As shown, during firing, the particles 42 sinter to form fingers 26 having a width W1 and a height H1. Typically, these dimensions are smaller than the paste 32 after dispensing (see Figure 4) has a corresponding width W2 and height H2, for example Figure 4 26. After firing / sintering, the width W2 of the paste 32 is reduced to the width W1 of the fingers 26. In addition, the height H2 of the paste 32 is reduced from firing / sintering to H1. The reduction in height is due at least in part to the reaction / etching of the anti-reflective coating 20, as further described below. Dimensions such as H1 and W1 are controlled by factors including, for example, if screen printing, (i) printer settings (e.g., squeegee pressure and speed), (ii) paste rheology and composition, (iii) screen parameters (e.g., opening size), and (iv) firing conditions.

[0200] Although the paste 32 initially includes oxide particles 50 and 52, the fingers 26 are metallic because some or all of the oxide particles are reduced during firing of the paste 32. The fingers 26 may be free of internal oxides, except for the outer air-exposed surfaces of the fingers 26 that may form native oxides (e.g., CuO and / or Cu2O, Sb2O3, etc.) when exposed to air. During sintering, the particles and reaction products, particularly metal from the nanoparticles 50 and metal from the second oxide particles 52, penetrate the antireflective coating 20 along with the copper-containing particles 46. During sintering, the metal, nanoparticles 50 and / or second oxide particles 52 and / or the metal of those oxide particles contact the antireflective coating 20 and may produce reaction products of the metal with the material of the coating 20. For example, when the antireflective coating 20 is SiN, the reaction products may include metal silicides and / or metal nitrides. These reaction products may form interfaces 58 (generally at 100°C) between the copper or copper-containing grains of the fingers 26 and the wafer 14. Figure 6 ) and may include silicide. After penetrating the anti-reflective coating 20, the composite of metals from oxide particles 50, 52 and 56 and copper-containing particles 46 that eventually form fingers 26 is electrically connected to the n-type region 16 of the wafer 14. Interface 58 can prevent copper from diffusing into the silicon of the wafer 14 during the manufacture and use of the solar cell 12. Interface 58 can form a boundary between copper or copper-containing grains and the silicon of the wafer. The composition of the grain boundary at interface 58 can include lead, nickel, copper, cobalt, manganese, antimony, tellurium and bismuth and / or another metal found in the nanoparticles 50 or the second oxide particles 52. In one embodiment, the back conductor 30 (e.g., aluminum) is co-fired with the paste 32 in air. Therefore, both the fingers 26 and the back conductor 30 can be fired simultaneously or separately. It should be noted that as the target width W1 of the fingers 26 decreases, the surface area of ​​the copper-containing particles can be reduced.

[0201] As reference Figure 4As shown, paste 32 includes a plurality of particles 42. Each of these particles may be synthesized prior to its introduction into organic vehicle 44. As an example, nanoparticles 50 may be synthesized from various metal salts. Fig. 7A and Figure 7B An exemplary flow chart for synthesizing nanoparticles 50 that may be included in paste 32 is shown.

[0202] exist Fig. 7A In the exemplary process shown, Cu / Ni / Pb nanoparticles 50 are synthesized. As shown, in a reactor 60, a first aqueous stream 62 of copper nitrate and ammonium hydroxide is added and stirred. The ammonium hydroxide precipitates copper hydroxide and a metal ammine complex. A second stream 64 of an aqueous dispersion of sodium borohydride is added to the reactor 60 at a predetermined rate and the solution is stirred. The reaction produces copper oxide / hydroxide nanoparticles 50.

[0203] Where additional coatings are desired on the copper oxide / hydroxide cores, additional streams are added to the reactor 60 containing the copper oxide / hydroxide nanoparticles. For example, where a nickel oxide coating is desired on the copper oxide / hydroxide nanoparticles, a third stream 66 of aqueous nickel chloride and aqueous sodium borohydride is added to the reactor 60 and stirred. This coats the copper oxide / hydroxide nanoparticles with a nickel oxide layer. A third layer of lead oxide / hydroxide is coated on the nickel oxide layer by adding a fourth stream 68 of aqueous lead nitrate to the reactor 60. This produces a lead oxide / hydroxide coating on the nickel oxide.

[0204] The following are Fig. 7A Possible reactions and side reactions occurring during the synthesis are shown.

[0205] Equation 1.

[0206] The primary stoichiometric reaction occurs in the reactor.

[0207] 2Cu(NO3)2(aq)+4NaBH4(aq)→

[0208] 2Cu(s)+4Na(NO3)(aq)+2B(OH)3(aq)+H2(g)+B2H6(g)

[0209] Equation 2.

[0210] Assume that excess NaBH4 reacts with H2O. In one process, substoichiometric amounts are used.

[0211] NaBH4(aq)+4H2O→NaB(OH)4(aq)+4H2(g)

[0212] Equation 3.

[0213] Assume that B2H6 reacts completely with H2O and all Cu is reduced to Cu2O in the presence of added NiCl2.

[0214] B2H6(g)+6H2O(l)→2B(OH)3(aq)+6H2(g)

[0215] Equation 4.

[0216] Equation 4a.

[0217] Cu has a multivalent nature and can be 2+ Ionic reaction.

[0218] Cu(s)+Cu 2+ (aq)→2Cu + (aq)

[0219] Equation 4b.

[0220] Cu + Can react with Cl- ions.

[0221] cu + (aq)+Cl - (aq)→CuCl(s)

[0222] Equation 4c.

[0223] CuCl can form Cu2O.

[0224] 2CuCl(s)+H2O(l)→2HCl(aq)+Cu2O(s)

[0225] Equation 5.

[0226] NiCl2 reacts with NaBH4 to coat the Cu2O particles with Ni.

[0227] 2NiCl2(aq)+4NaBH4(aq)→2Ni(s)+4NaCl(aq)+2B(OH)3(aq)+H2(g)+B2H6(g)

[0228] Equation 6.

[0229] When Pb(NO3)3 is added, a substitution reaction occurs.

[0230] 3Ni(s)+2Pb(NO3)3(aq)→3Ni(NO3)2(aq)+2Pb(s)

[0231] Both the Ni and Pb shells can be oxidized to NiO and PbO. Less than stoichiometric amounts may be used in the reaction. If so, assuming that NaBH4 becomes the limiting factor, Equation 1 becomes Equation 7 and Equation 5 becomes Equation 8.

[0232] Equation 7.

[0233] Non-stoichiometric reactions occur in batch reactors.

[0234] 0.37Cu(NO3)2(aq)+0.74NaBH4(aq)→

[0235] 0.37Cu(s)+0.74Na(NO3)(aq)+0.37B(OH)3(aq)+0.185H2(g)+0.185B2H6(g)

[0236] The mass balance also assumes that there is no excess NaBH4 to react with H2O. The reaction in Eq. 2 is assumed not to occur.

[0237] Equation 8.

[0238] A non-stoichiometric reaction of NiCl2 with NaBH4 to coat Cu2O particles with Ni.

[0239] 0.1NiCl2(aq)+0.2NaBH4(aq)→

[0240] 0.1Ni(s)+0.2NaCl(aq)+0.1B(OH)3(aq)+0.05H2(g)+0.05B2H6(g)

[0241] Equation 9.

[0242] When Pb(NO3)2 is added, a substitution reaction occurs.

[0243] 0.1Ni(s)+0.2Pb(NO3)3(aq)→0.1Ni(NO3)2(aq)+0.07Pb(s)+0.13Pb(NO3)3(aq)

[0244] For non-stoichiometric amounts, Equation 3 becomes Equation 10.

[0245] Equation 10.

[0246] Reaction of B2H6 with H2O.

[0247] 0.235b2H6(g)+1.41H2O(l)→0.47B(OH)3(aq)+1.41H2(g)

[0248] After addition and reaction, the nanoparticles 50 are separated from the supernatant by centrifugation at 70. And, the solid residue, which is the Cu / Ni / Pb nanoparticles, is dried at 72. The nanoparticles 50 may be crushed to separate agglomerates, then sieved and ready for use in the paste 32.

[0249] Figure 8 Describes the basis Fig. 7A Transmission electron microscope images of three different Cu / Ni / Pb nanoparticles produced by the process shown. As shown, energy dispersive X-ray maps for Cu are shown in (b), (h), and (n); for oxygen are shown in (e), (i), and (p); for Ni are shown in (d), (j), and (p); for Cl are shown in (e), (k), and (q); and for Pb are shown in (f), (l), and (r). The elemental map generally shows that C in the nanoparticle 50 u , O, and Ni are present and uniformly distributed. Pb and Cl appear to have a more irregular distribution.

[0250] Figure 7B A similar process is shown in FIG. However, the nanoparticles 50 produced are Ni / Ni / Pb nanoparticles. That is, the core of the nanoparticle is nickel oxide, with a nickel oxide coating, and then a lead oxide coating. Growing the nickel oxide in two stages produces a larger particle size. In this regard, a first stream 74 of nickel nitrate and ammonium hydroxide is added to the reactor 60. Subsequently, the nickel nitrate and ammonium hydroxide are added in a manner similar to that described in reference 7. Fig. 7A The second stream 64, followed by the third stream 66 and the fourth stream 68 are added to the reactor 60 in the manner described. After centrifugation 70 and drying 72, the Ni / Ni / Pb nanoparticles 50 are ready for addition to the paste 32.

[0251] Reference Fig. 9A In one embodiment, the copper-containing particles 46 are surface-modified with a metal oxide prior to mixing with the paste 32. Fig. 9A In the flow chart of , copper-containing particles 46 are placed in a reactor 76. The copper-containing particles 46 can be pretreated with oleic acid, or the particles 46 can be untreated before being placed in the reactor 76. A metal salt (e.g., nickel nitrate) is dissolved in an aqueous ethylene glycol solution containing polyvinyl pyrrolidone. The solution of dissolved metal salt and ethylene glycol is injected into the reactor 76 as a first stream 80 and mixed with an aqueous dispersion of a reducing agent, such as sodium hypophosphite (NaPO2H2), as a second stream 82. The solution is continuously stirred and heated in the reactor 76 for a prescribed time. The metal ions are reduced at an elevated temperature, and the resulting reaction produces a solution of copper-containing powder coated with a metal or metal oxide / hydroxide. As an example, in Fig. 9AIn the embodiment of the present invention, the copper-containing particles 46 are coated with nickel oxide and / or nickel hydroxide. The particles 56 may coat or decorate the particles 46. It should be noted that the nickel oxide / hydroxide may contain phosphorus and may depend on the concentration of the reducing agent added to the reactor 76. The coated particles 46 are separated from the solution at 84 (e.g., by a centrifuge) and then dried at 86.

[0252] Although the reference Fig. 9A Nickel salts are described, but various other metal salts can be used to treat the copper-containing particles 46. As an example, the coating on the copper-containing particles 46 can include cobalt (Co) and / or manganese (Mn), etc. By adding the copper-containing particles 46 to the reactor 76, the surface of the copper-containing particles 46 can be coated with particles 56. The amount of coating 56 can be controlled by the time the mixture is kept above a specific temperature. Generally, as time and temperature increase, the surface area of ​​the copper-containing particles 46 coated with particles increases. For example, the total surface area of ​​the copper-containing particles 46 with particle-coated surfaces increases. Typically, the surface area of ​​the copper-containing particles 46 covered by the particles is increased by at least 10% and can be as high as 3,000% over the uncovered particles 46.

[0253] Each of the above particles 42 is then mixed with an organic vehicle 44. Fig. 9B , the organic vehicle 44, the nanoparticles 50, the second oxide particles 52 and the copper-containing particles 46 are mixed to form a screen-printable paste 32. Fig. 9B As shown, the organic vehicle 44 comprises polyvinyl pyrrolidone dissolved in a solvent (e.g., polyethylene glycol) and added at 90 to a vacuum mixer 92. Nanoparticles, such as those from Fig. 9A The Cu / Ni / Pb nanoparticles 50 are also placed in the vacuum mixer 92 at 94. The nanoparticles 50 and the organic vehicle 44 are mixed under vacuum for a specified time. At 96, the second oxide particles 52 are placed in the vacuum mixer 92. The mixture is then mixed under vacuum. At 98, the copper-containing particles 46 are placed in the vacuum mixer 92 and mixed under vacuum. When present, at 100, additional copper-containing particles 46 are placed in the vacuum mixer 92 and mixed under vacuum. Fig. 9B In the embodiment shown, particles 42 in streams 94, 96, 98, 100 are added to vacuum mixer 92 in a predetermined order based on surface area. In the exemplary embodiment, particles 42 having the largest surface area are added first.

[0254] Once all of the carrier 44 and particles 42 have been added to the vacuum mixer 92, the mixture is mixed under vacuum for a specified time. The mixture is then ground at 102. This can include using a triple roll mill, a ball mill, or other particle dispersion equipment. The grinding process helps to separate particle agglomerates and promote homogenization and degassing of the mixture. After roller milling, the mixture is aged at 104 at an elevated temperature (e.g., 100° C.) for a specified length of time to improve the wetting of the organic carrier 44 on the particles 42. The mixture can then be subjected to another round of roller milling at 106, and additional organic carrier 44 (not shown) can be added to reach a predetermined viscosity before the paste 32 is ready for use.

[0255] In order to facilitate a more complete understanding of the present invention, the following non-limiting examples are provided.

[0256] Example

[0257] In the following examples, the powder may be doped with phosphorus (P) or another element. This is represented by the symbol Cu / element symbol "(?)P", such as "Cu / Ni(?)P", which means that copper-containing particles having nickel on their surface may be doped with phosphorus. It is considered that the copper or nickel material (in the form of metal, oxide or hydroxide) is doped with P. The embodiments of the present invention are not limited to those doped with P or any other element.

[0258] Example 1. Synthesis of Copper-Containing Particles with Nickel

[0259] The synthesis of copper particles with nickel-containing microparticle coated surfaces is illustrated by the following example. 4.50 g of polyvinyl pyrrolidone (PVP) MW 40,000 was dissolved in 300 mL of ethylene glycol in a 2000 mL flask. The mixture was stirred with a paddle mixer. The mixture was prepared one day before use. 144.78 g (0.5 mol) of nickel nitrate hexahydrate was added to the PVP / ethylene glycol mixture and mixed until dissolved. 381.24 g (6.0 mol) of copper powder was gradually added to the mixture (Example 1 was performed with each of the following copper powders: 1.) 10 μm to 22 μm, 2.) 7.5 μm to 14.7 μm, 3.) 1.8 μm to 7.7 μm, 4.) 1.2 μm to 3.2 μm). The mixture was continuously mixed between additions to prevent the formation of lumps. The mixture was stirred with a paddle mixer for 30 minutes. To the mixture were added 216.24 g (2.0 mol) of sodium hypophosphite monohydrate and 150 mL of distilled water. The mixture was stirred with a paddle mixer for 30 minutes.

[0260] An aluminum foil lid with holes for a paddle mixer was placed around the top of the beaker. The beaker was placed on a hot plate, the hot plate temperature was increased to 350° C. and the mixture was heated for 40 minutes with constant stirring by a paddle mixer. The mixture was allowed to reach 90° C. After 40 minutes, the hot plate was turned off.

[0261] Allow the mixture to cool and transfer to a centrifuge container. Centrifuge the material at 3000 rpm for 3 minutes. Discard the supernatant into a waste bottle. Add more mixture to the centrifuge container (or add distilled water if the mixture beaker is empty). Stir and shake the bottle thoroughly. Repeat centrifugation and decantation until the supernatant is clear and colorless. Place the solid particles on a drying tray and allow to dry overnight.

[0262] The dried copper-containing particles coated with nickel oxide / hydroxide were crushed with a grinder and sieved through a 325 mesh screen.

[0263] The following equation is considered to be the reaction that occurs during synthesis. Nickel oxide will be deposited on the surface of the copper.

[0264] Equation 1. The main stoichiometric reaction occurring in a batch reactor. Nickel nitrate is the rate limiting reagent.

[0265] Ni(NO3)2(aq)+2NaH2PO2(aq)+2H2O→Ni(s)+2Na(HPO3)(aq)+3H2(g)

[0266] Example 2. Synthesis of Copper-Containing Particles with Cobalt

[0267] The synthesis of copper particles with a surface coated with cobalt-containing particles is illustrated by the following example. The metal used in the coating can be changed by replacing the metal salt in Example 1 with cobalt nitrate hexahydrate. 4.50g of polyvinyl pyrrolidone (PVP) 40,000 was dissolved in 300mL of ethylene glycol in a 2000mL flask. The mixture was stirred with a paddle mixer. The mixture was prepared one day before use. 145.52g (0.5mol) of cobalt nitrate hexahydrate was added to the PVP / ethylene glycol mixture and mixed until dissolved. 381.24g (6.0mol) of copper powder was gradually added to the mixture (Example 2 was carried out using copper powder with a size distribution of 10μm to 22μm and 1.2μm to 3.2μm, respectively). The mixture was continuously mixed between additions to prevent the formation of lumps. The mixture was stirred with a paddle mixer for 30 minutes. 216.24g (2.0mol) of sodium hypophosphite monohydrate and 150mL of distilled water were added to the mixture. The mixture was stirred with a paddle mixer for 30 minutes.

[0268] An aluminum foil lid with holes for a paddle mixer is placed around the top of the beaker. The beaker is placed on a hot plate, the hot plate temperature is increased to 350°C, and the mixture is heated for 40 minutes with constant stirring by a paddle mixer. The hot plate is set at 350°C and the mixture is allowed to reach the desired temperature of 90°C. The hot plate is turned off after 40 minutes. The mixture is allowed to cool.

[0269] The mixture was transferred to a centrifugal container and centrifuged at 3000 rpm for 3 minutes. The supernatant was discarded into a waste bottle. Centrifugation and decantation were repeated until the supernatant was clear and colorless. The solid particles were emptied into a dry pan and dried overnight. The dried particle-coated copper powder was crushed with a grinder and sieved through a 325 mesh sieve.

[0270] Example 3. Synthesis of copper-containing particles with manganese

[0271] The synthesis of copper particles with manganese-containing microparticles coated on the surface is illustrated by the following examples. The metal used in the coating can be changed by replacing the metal salt in Example 1 with manganese nitrate tetrahydrate. 4.50g of polyvinyl pyrrolidone (PVP) 40,000 was dissolved in 300mL of ethylene glycol in a 2000mL flask. The mixture was stirred with a paddle mixer. The mixture was prepared one day before use. 125.51g (0.5mol) of manganese nitrate tetrahydrate was added to the PVP / ethylene glycol mixture and mixed until dissolved. 381.24g (6.0mol) of copper powder (Example 3 was performed with each of 10μm to 22μm copper powder and 1.2μm to 3.2μm copper powder, respectively) was gradually added to the mixture. The mixture was continuously mixed between additions to prevent the formation of lumps. The mixture was stirred with a paddle mixer for 30 minutes. 216.24g (2.0mol) of sodium hypophosphite monohydrate and 150mL of distilled water were added to the mixture. The mixture was stirred with a paddle mixer for 30 minutes.

[0272] An aluminum foil lid with holes for a paddle mixer is placed around the top of the beaker. The beaker is placed on a hot plate, the hot plate temperature is increased to 350°C and the mixture is heated for 40 minutes with constant stirring by a paddle mixer. In one embodiment, the hot plate is set at 350°C and the mixture is brought to 90°C. After 40 minutes, the hot plate is turned off and the mixture is allowed to cool.

[0273] The mixture was transferred to a centrifuge container and centrifuged at 3000 rpm for 3 minutes. The supernatant was discarded into a waste bottle. The decantation and centrifugation were repeated until the supernatant was clear and colorless. The solid particles were emptied into a drying pan and dried overnight.

[0274] The dried powder was crushed with a grinder and sieved through a 325 mesh screen.

[0275] Example 4. Modification of the surface area of ​​copper-containing particles with nickel

[0276] The surface area of ​​the coated copper powder is controlled by varying the reaction time during the synthesis. The surface area of ​​the coated powder is directly related to the time the reaction mixture is kept above the reaction temperature. When the reactants are kept above this temperature, the amount of deposited material increases, which increases the surface area of ​​the copper powder. Fig.10 Table 1 shows the effect of reaction temperature and time on the surface area of ​​1.2 μm to 3.2 μm copper powder subjected to coating consistent with Example 1.

[0277] Table 1

[0278]

[0279] The peak temperature in the reactor and the time the reaction mixture is maintained above 85°C increase the surface area of ​​the coated copper powder. In this example, the increase is 38% at 90°C and up to 5 times at 104°C.

[0280] The surface area of ​​the coated powder is also related to the maximum temperature experienced by the reactants during the reaction. Reactions using fine (1.2 micron to 3.2 micron) copper powder with an oleic acid coating are susceptible to temperature overshoots, where the copper powder with an oleic acid coating can foam during the reaction. The peak temperature is controlled by the time the hot plate is turned off.

[0281] Gaseous byproducts were trapped within the foam layer. At peak temperatures below 90°C, the foam layer collapsed during cooling. In addition to the powder having a lower surface area, the material also showed signs of oxidation (see Table 1). For reactions with higher peak temperatures, the foam layer remained above the reaction mixture until the material was ready for centrifugation.

[0282] When the reaction temperature exceeded 100°C, the foam layer collapsed once the reaction reached the peak temperature, thereby reducing the thickness of the foam layer. This reduction in thickness produced a faster cooling rate for the reaction in addition to a slightly faster stirring rate. When the heating and cooling curves for the laboratory scale reaction were within a few degrees (i.e., could be directly superimposed), the measured surface area of ​​the coated copper (comparing the two batches) was within 0.002 m 2 / g. However, even under matched heating and cooling conditions, the delay before centrifuging the material (about 1.5 hours) would have kept the gas trapped in the foam for a longer period of time. Thus, the surface area of ​​the coated material was found to increase by 0.126 m 2 / g.

[0283] FIG. 11A to FIG. 11DThe performance of a paste containing unmodified copper powder with Ni / Ni / Pb nanoparticles and Sb2O3 particles is shown. These figures illustrate the effect of accelerated aging at 200°C on (a) the short circuit current density J sc ( Fig.11A ), (b) open circuit voltage V oc ( Fig. 11B ), (b) Filling factor FF( Fig. 11C ) and (d) efficiency η( Fig.11D ). Paste 1 was formulated with Sb2O3 and 100% Ni / Ni / Pb nanoparticles. See Table 12 (below). The copper powder was uncoated. The results were normalized to their initial value at 0.01 hour. The error bars are the standard deviation of the results from 5 cells.

[0284] Examples 5 to 9. Durability Testing Methods for Devices Metallized with Copper-Containing Pastes

[0285] The durability of fired solar cells is measured by monitoring the open circuit voltage (V oc ) to determine. Constant V oc Indicating that the copper has not penetrated into the silicon. To speed up the test, the cells are exposed to high temperatures. One test method follows a peer-reviewed academic article on electroplated copper contacts on silicon solar cells. This test thermally stresses the cell at elevated temperatures of 150°C to 300°C to assess the reliability of the cell over a much shorter period of time. These temperatures are above the maximum operating temperature range of 80°C to 90°C for solar cells. One of the disadvantages of this test method is that the test temperatures are high enough that there could be chemical interactions between the materials that would never occur during normal operation of the solar cell. Diffusion of copper into the junction will cause V oc decline.

[0286] Example 5. Effect of Nanoparticle Composition on Durability

[0287] Three copper-containing pastes were compared. Paste 2, Paste 3, and Paste 4 were formulated as shown in Table 2 (below). The nanoparticle components of the pastes consisted of (i) 100% Cu / Ni / Pb nanoparticles, (ii) 50% Cu / Ni / Pb nanoparticles and 50% Ni / Ni / Pb nanoparticles, and (iii) 100% Ni / Ni / Pb nanoparticles, respectively. Fig. 12A The effect of nanoparticle composition on PV performance (i.e., open circuit voltage, V) after thermal stressing the cells at 200°C for up to 110 hours is illustrated for cells made from each of Paste 2, Paste 3, and Paste 4. oc )’s impact. Fig. 12AThe error bars in are the standard deviation between 4 to 6 cells measured for each paste. The results are normalized to their initial values ​​at 0.01 hours.

[0288] Fig. 12B , Fig. 12C , Fig.12D and Fig.12E The effects of accelerated aging on PV performance are illustrated, where Fig. 12B and Fig.12D 100% Cu / Ni / Pb nanoparticles, Fig. 12C 50% Cu / Ni / Pb nanoparticles and 50% Ni / Ni / Pb nanoparticles, Fig.12E It is 100% Ni / Ni / Pb nanoparticles.

[0289] Fig.12F , Figure 12G , Fig.12H and Fig.12I The effect of accelerated aging at 200°C on (a) the short-circuit current density J sc ( Fig.12F ), (b) open circuit voltage V oc ( Figure 12G ), (c) Filling factor FF( Fig.12H ), and (d) efficiency η( Fig.12I ). The results are normalized to their initial values ​​at 0.01 hours. The error bars are the standard deviation of 4 to 6 cells measured for each paste.

[0290] Table 2

[0291]

[0292] Example 6. Effect of surface modification of copper-containing powder on durability

[0293] This example illustrates the effect of a microparticle coating containing copper powder on the PV performance of crystalline silicon cells from three different manufacturers. The copper powder used a coating consistent with Example 1. The prepared cells were thermally stressed at 200°C for up to 110 hours. The properties of Paste 5 of Table 3 are shown in FIG. 13A to FIG. 13H .

[0294] Table 3

[0295]

[0296] Example 7. Effect of the relative ratio of the second oxide particles and nanoparticles in the paste on durability

[0297] This example illustrates the effect of varying the proportion of second oxide particles in the paste by varying the ratio of Ni / Ni / Pb nanoparticles relative to the ratio of second oxide particles.The weight ratio of the two particle types was kept constant at 2.50. Fig.14A , Fig. 14B and Fig. 14C PV performance of monocrystalline silicon solar cells is shown, where fingers were printed with the following pastes from Table 4 (below): (a) Paste 6, (b) Paste 7, and (c) Paste 8.

[0298] The cells were thermally stressed at 150°C for up to 300 hours. The proportion of nanoparticles and second oxide particles in these pastes was increased such that the volume of copper (solids only) in the pastes ranged from 85.50 vol% to 79.51 vol% Cu. The thickness of the glassy interface between the fingers and the wafer increased as the proportion of nanoparticles and second oxide particles in the paste increased. The PV performance of the cells during the accelerated aging test was maintained by keeping the solids only portion of the paste greater than 80 vol%.

[0299] Table 4

[0300]

[0301] The effect of accelerated aging tests at 150°C on the IV performance of monocrystalline silicon cells with a passivated emitter and rear cell (PERC) localized aluminum back surface field (Al BSF) metallized with paste is shown in Fig.14A , Fig. 14B and Fig. 14C middle.

[0302] Example 8. Effect of the relative proportion of the second oxide in the paste on durability

[0303] This example shows the effect of the proportion of second oxide particles in the paste on the cell performance during accelerated aging tests at 150°C up to 200 hours. The weight ratio of second oxide particles to nanoparticles in the paste was varied by varying the proportion of second oxide particles in the paste used to print the fingers. The total surface area contribution of the coated copper-containing powder used in the paste was fixed at 0.74 m2 / g of paste. 2 Table 5 shows the composition of the paste used to print the fingers. The same busbar paste formulation was used for all cells.

[0304] Table 5

[0305]

[0306] Fig.15A , Fig. 15B , Fig. 15C , Fig.15D , Fig.15E and Fig.15F The effect of accelerated aging tests at 150°C on the PV performance of monocrystalline Si cells with PERC localized Al BSF cells metallized with the pastes of Table 5 is shown. All pastes showed stable V oc Finger resistance and therefore fill factor (FF) was found to be affected by the second oxide to nanoparticle ratio of the paste. The best endurance performance was found using a ratio of 1.50. The data at second oxide / NP = 0.5 was discarded, probably due to the fact that the sample was small and the firing conditions were slightly off target.

[0307] Example 9. Effect of Surface Area of ​​Copper-Containing Particles with Nickel on Durability

[0308] The nickel coating on the copper-containing powder was quantified by measuring the surface area of ​​the material. The amount of coating in the paste was varied by varying the surface area of ​​the fine copper powder in the paste. The amount of coating on the copper powder was (Paste 11) 0.74 m 2 / g paste, (paste 14) 0.83m 2 / g paste, (paste 15) 1.01m 2 / g paste, and (paste 16) 1.10m 2 / gram of paste. All pastes used a second oxide particle to nanoparticle ratio of 1.50. Table 6 shows the composition of the paste used to print the fingers. All cells used the same busbar paste recipe.

[0309] Table 6

[0310]

[0311] Fig.16A , Fig. 16B , Fig. 16C , Fig.16D and Fig.16E The normalized PV performance of monocrystalline Si cells with PERC localized Al BSF metallized with the pastes in Table 6 is shown in Figure 6, respectively, after accelerated aging test at 200°C. sc , normalized V oc , normalized FF, normalized η, and normalized resistance over the entire finger. When the surface area of ​​the copper-containing particles with nickel is greater than 1.0 m 2 / g paste, the resistance of the fingers increased significantly; therefore, the FF decreased. 2 / g paste surface area, yielding the lowest FF reduction during the test period ( Fig. 16C ).

[0312] Fig.17A , Fig. 17B , Fig. 17C and Fig.17D The results show that at 200°C Fig.16A , Fig. 16B , Fig. 16C , Fig.16D and Fig.16E 1 . When the surface area of ​​the copper-containing particles in the paste is low (Paste 11), the diffusion barrier formed by the paste appears to be insufficient and a significant increase in the dark IV curve is observed; resulting in lower FF and performance. However, when the surface area is high (Paste 16), the series resistance of the device increases significantly, indicating that the barrier is too thick and becomes more resistive under the test conditions.

[0313] Example 10. Effect of copper particle surface area on etching and fill factor

[0314] This example illustrates the effect of the surface area of ​​the copper-containing particles used in the paste on the etching function of the paste. Both the second oxide particles and the nanoparticles are capable of etching a silicon nitride (SiN) antireflective coating. As the surface area contribution of the copper-containing particles increases, it is believed that the ability of the paste to etch through the SiN layer decreases. The surface area contribution from the copper-containing particles is changed by changing the ratio of coarse copper-containing powder to fine copper-containing powder in the paste. Table 7 lists the effect of changing the ratio on the surface area contribution of the copper-containing powder and its effect on the bulk resistivity, contact resistivity and FF of the device. The paste listed in Table 7 includes nanoparticles having a Cu / Ni / Pb composition. In theory, during firing, the nanoparticles (Cu / Ni / Pb nanoparticles) and the Sb2O3 second oxide particles melt and coat the surface of the copper-containing particles. Therefore, the greater the surface area contribution of the copper-containing particles, the smaller the proportion of the nanoparticles reaching the surface of the battery and the second oxide from the second oxide particles. All samples were fired using a refractory brick method. The refractory brick method is a technique in which the sample battery is placed on a hot plate set at 300°C for 3 minutes. The sample cell was then immediately transferred to a muffle furnace set at 750°C to 800°C for 1 to 3 seconds. The furnace was stacked with refractory bricks to keep the heat in while the furnace door was open. The sample cell was placed directly on the surface of the refractory bricks, and the door was closed during the time the sample was in the furnace.

[0315] Table 7

[0316]

[0317] The etching process is controlled by the amount of lead (Pb) in the paste, which can be introduced into the paste via nanoparticles (e.g., Ni / Ni / Pb nanoparticles). The molar ratio of Ni:Pb used for the synthesis is 14:1. This amount of lead is sufficient to contain 0.83 m2 Cu / g paste is sufficient to etch through SiN x The raw copper flakes were replaced by fine (1.2 μm to 3.2 μm) copper-containing powder to obtain a 2.73 μm 2 Therefore, it is believed that the amount of lead in the paste needs to be increased to etch through the SiN x layer. One solution is to increase the loading of Ni / Ni / Pb nanoparticles in the paste. For this 3.3-fold increase in copper surface area, the molar ratio of Pb to Cu (Pb / (Pb+Cu)) needs to be increased by a factor of 12. Increasing the amount of nanoparticles in the paste was considered impractical due to the possible negative impact on the printability of the paste. In addition, the volume of copper-containing particles in the printed contacts is reduced, which affects the resistivity ρ. Therefore, the Ni / Ni / Pb nanoparticle synthesis was improved (Ni:Pb=1.6:1) so that the nanoparticles contained a higher proportion of Pb. Subsequently, the amount of nanoparticles in the paste was only increased by a factor of about 2.5.

[0318] Although the paste containing 100% fine (1.2 μm to 3.2 μm) copper powder etches through the SiN x , but the battery ρ c Still high (0.426Ωcm 2 ). High ρ c The main reason is cracking in the fingers affecting the measured resistance. It is believed that the cracking is due to shrinkage caused by densification. To solve this problem, rough copper flakes were used in the paste. The total surface area of ​​copper in the paste was kept at 2.73 m 2 The amount of binder and solvent in the organic vehicle was adjusted based on the proportion of solids in the paste.

[0319] Fig.18A , Fig.18B and Fig. 18C The effect of the ratio of coarse (10 μm to 20 μm) copper to fine (1.2 μm to 3.2 μm) copper on the surface area, volume, and weight contribution of copper with nickel is shown. The ratio has an impact on the bulk resistivity (ρ) and contact resistivity (ρ c ) Fig.19A and Fig.19B shown. Fig.18D and Fig.18EImages of fired pastes using 100% fine powder and 100% coarse powder are shown separately. The paste containing only fine copper-containing powder resulted in the formation of large cracks due to the densification process that occurs during firing. As the amount of coarse copper flakes increases, the cracking in the fingers decreases. This is due to the ability to load more copper-containing particles into the paste, thereby increasing the volume of copper without increasing the total surface area contribution from the copper. When a 70:30 coarse copper powder to fine copper powder ratio was used, 3.68×10 -5 ρ value of Ωcm.

[0320] Example 11. Effect of the shape of copper-containing particles on the rheology and formulation of the paste

[0321] This example shows the effect of the shape of the raw copper powder on the paste rheology, microstructure and formulation. In this example, the effect of the raw spherical particles is compared with the raw flake particles. The shape and packing of the spherical copper-containing particles causes the nanoparticles and the second oxide particles (Sb2O3) to melt and flow to the SiN much faster than the interconnected porous structure of the raw copper flakes. x layer. Therefore, the amount of nanoparticles and second oxide particles can be reduced; thereby allowing the paste containing spherical particles to have a higher solid loading and relatively lower viscosity even if the paste contains a higher proportion of fine copper-containing particles. The PV performance, viscosity and microstructure are shown in Fig. 20A and Fig. 20B , Fig. 20C ,as well as Fig.20D and Fig.20E Further investigation of the composition of the second oxide revealed that c Reduced to 0.065Ωcm 2 .

[0322] Table 8

[0323]

[0324] Table 8 compares Paste 4 and Paste 17. Fig. 20A , Fig. 20B and Fig. 20C The IV performance of those pastes were compared for: (a) a 90:10 mixture of (10μm to 22μm) coarse copper powder and fine (1.2μm to 3.6μm) copper powder and (b) a 70:30 mixture of (10μm to 22μm) spherical copper powder and fine (1.2μm to 3.6μm) copper powder. The cells were measured using a halogen lamp. A comparison of the volume percentage and viscosity of the pastes using coarse (10μm to 20μm) copper flakes and (10μm to 22μm) spherical copper powder is shown. Fig.20D and Fig.20E In the figure, SEM images of fired fingers from (d) coarse powder and (e) large spherical powder are shown, respectively.

[0325] Example 12. Study on the accumulation of copper-containing particles of different shapes

[0326] In order to print fingers with the lowest possible resistivity, it is desirable that the particles in the paste be packed as closely together as possible with minimal void space. The shape and size of the particles, as well as the amount of organic vehicle in the paste will determine how closely the powder will pack. Table 9 provides estimates of the apparent tap density of different particles used in the paste. The smaller the particle size or the larger the particle surface area, the lower the packing density.

[0327] Table 9

[0328]

[0329]

[0330] Table 10

[0331]

[0332] Table 10 shows the ratios of different powders used in selected pastes. Fig.21A , Fig. 21B and Fig. 21C Images of squares printed with the following pastes (a) Paste 18, (b) Paste 19, and (c) Paste 20 are shown, respectively. The prints fell off the silicon substrate due to densification and shrinkage. The squares were placed on a light box to observe the porosity of the fired prints. Squares printed with a higher proportion of fine powder produced a denser structure.

[0333] Fig. 22 is a SEM cross-sectional image of a finger printed with the paste specified in Table 10 (above). Fig. 22 , the pastes are (a) paste 2, (b) paste 5, (c) paste 41, (d) paste 1, (e) paste 21, (f) paste 22, (g) paste 23, (h) paste 24, and (i) paste 25. For pastes containing a higher proportion of fine powder and a wide range of particle sizes, a denser cross-section is obtained.

[0334] Table 11 (below) shows the Fig. 22 (b) shows the overall paste composition of paste 5. Table 12 shows the compositions of Tables 10 and Fig. 22The paste number shown in (d) is the entire paste composition of paste 1. Paste 1 is formulated so that it contains the same ratio of second oxide particles to nanoparticles to copper-containing particles in the paste as used in paste 5. However, in order to produce a denser cross-section, four different sizes of copper powder (Cu112SP, 610, 603 and C1-2000) are used. It is assumed that the mixing and grinding process will allow the Cu112SP, 610 and 603Cu powders to stack with a stacking factor Φ (random Φ) of 0.639. The combined weight of the Cu112SP, 610 and 603 powders is taken to have 70 wt% copper powder. C1-2000 is added at 30 wt% (of the total copper). The Cu / NP weight ratio is kept constant, with PVP=0.0164 gPVP / g solid. The microstructures of the fingers printed with paste 1 appear to be denser than those of paste 5.

[0335] Table 11 – Paste number: Paste 5

[0336]

[0337] Table 12 – Paste Number: Paste 1

[0338]

[0339] Example 13. Effect of organic binder on oxides in reduction paste and its effect on firing conditions

[0340] Some of the metal in the paste, especially in the nanoparticles and in the coating on the surface of the copper-containing powder, is in the form of an oxide. Introducing oxides into the electrical contacts of the cell will increase the resistivity of the fingers and will reduce the short-circuit current density (J sc ), fill factor (FF), and overall efficiency (η). However, oxides are advantageous because their synthesis is simpler and the increased surface area is useful during etching of the anti-reflective (SiN) layer. These materials must be reduced during firing due to the impact on the overall performance of the solar cell device. Typical techniques for reducing oxides during synthesis include the use of hydrogen reducing agents such as hydrazine, sodium borohydride, and the like. Synthetic gas is also a common reducing agent, but it requires a specialized furnace. Organic carriers such as polyvinyl pyrrolidone (PVP) decompose at temperatures in excess of 300°C. The decomposition produces a reducing gas that is capable of reducing metal oxides to metals in the paste. This allows the paste to be fired in air while reducing selected oxides present in the paste. The exemplary pastes described herein can be used in furnaces commonly used in the PV industry.

[0341] Fig.23 The X-ray diffraction patterns (XRD) of films formulated with Cu / Ni / Pb nanoparticles, lead oxide and PVP are shown. Table 13 below lists Fig.23The composition of the paste in the film. The deposited film clearly shows strong reflections of cuprous oxide (Cu2O) and lead oxide (PbO2). In this case, the film is subjected to a rapid firing process called intense pulsed light (IPL) treatment (also known as photon sintering). The IPL treatment applies multiple light pulses to a given sample in rapid succession. The temperature rise experienced by the film depends on the amount of light applied and is a function of the thermal conductivity, specific heat capacity and density of the material. The initial light pulse is used to decompose the PVP in the film and reduce the metal oxide. Subsequent light pulses sinter and melt the particles into a reinforced film. The rapid heating process is combined with the PVP in the paste, resulting in allowing the sample to be heat treated in air. Fig.23 Also shown is the film after IPL treatment. The intensity of the oxide reflection has decreased and is replaced by a strong copper reflection, with the film preferentially oriented toward the Cu(111) peak position. In addition, nickel is also present.

[0342] Table 13

[0343]

[0344] Fig.24A and Fig. 24B An example of the effect of the binder on the etching function of the paste is shown. The paste is formulated with Cu / Ni / Pb nanoparticles and second oxide nanoparticles (antimony oxide). The amount of organic binder (PVP) in the paste is adjusted to change the weight % from 1.01 wt % to 3.02 wt %. The composition of the paste can be found in Table 14 below. The paste is printed on a monocrystalline silicon solar cell with an all-Al BSF back contact. The cells are all fired at 690°C for 3 seconds using the refractory brick method. Fig.24A and Fig. 24B The IV curve of the cell measured in the dark is shown. The low current under forward bias indicates that the paste has not etched through the SiN layer and made electrical contact with the silicon. The relatively high current from 0V to 0.5V indicates that the paste has etched too deeply. When the amount of PVP in the paste is low (1.11 wt %), the reducing gas is not enough to reduce all the oxides (nanoparticles and second oxides) in the paste and etch through the SiN coating. This results in a more resistive IV characteristic. As the amount of PVP in the paste increases to 3.02 wt %, the reducing environment caused by the decomposition of PVP is sufficient to reduce the oxides and etch through the SiN. Fig.24A and Fig. 24BThe effect of firing temperature on the ability of PVP to etch through the anti-reflective coating is also shown. The cell was printed with a paste containing 3.02 wt% PVP and fired using the refractory brick method. The cell was kept in the furnace for 3 seconds. The furnace temperature varied from 630°C to 720°C. At low temperatures, the energy input is insufficient to fully etch through the SiN and sinter the copper-containing particles. At higher temperatures (720°C), an increase in dark current is observed, indicating that the contact appears to have penetrated deeper into the emitter. These results suggest that the firing conditions can be adjusted by varying the amount of PVP in the paste.

[0345] Table 14

[0346]

[0347] FIG. 31A to FIG. 31D An example of the effect of PVP in a paste is provided. In this example, by varying the surface area of ​​fine copper-containing particles in the paste (e.g., 1.10 m 2 / g, 2.65m 2 / g and 4.14m 2 / g) to vary the surface area contribution from the copper-containing particles with nickel (i.e., the amount of nickel particle coating). The effect of the amount of organic binder (PVP) on these different paste compositions was also studied. Table 15 below lists the surface area contribution from the copper-containing particles with 1.10 m 2 The paste compositions of the pastes were prepared by mixing 1.5 wt %, 2.0 wt %, 2.5 wt % and 3.0 wt % of PVP. The effect of the wt % of PVP in the paste and the surface area of ​​the fine (1.2 μm to 3.6 μm) copper-containing particles on the electrical and PV performance of single crystal silicon solar cells ( Fig.31A , Fig.31F and Figure 31K -J sc ; Fig.31B , Figure 31G and Figure 31L -V oc ; Fig.31C , Fig.31H and Figure 31M –FF; Fig.31D , Fig.31I and Fig.31N –η; and Fig.31E , Fig.31J and Fig.31O – total resistance over the entire finger) is shown in Figure 24. The paste compositions were respectively 2 / g, 2.65m 2 / g and 4.14m 2 / g of fine copper powder listed in Table 14 Paste 31 ( FIG. 31A to FIG. 31E )、Paste 32( Figures 31F to 31J ) and paste 33( Figures 31K to 31O The cells were fired using the procedure described in Example 16 at a stage speed of 2.5 cm / sec and a zone 2 set point temperature of 753° C. The hold time in zone 2 varied from 4 to 8 seconds.

[0348] FIG. 31A to FIG. 31O It is shown that for low surface areas (e.g., 1.01 m 2 / g), a small amount (e.g., 1.5 wt%) of PVP is sufficient to reduce the oxides in the paste and etch through the SiN layer. The results also show that the hold time in zone 2 or the set point temperature in zone 2 can be further reduced to improve the PV performance of the device. Increasing the amount of PVP in these pastes resulted in reduced performance due to increased series resistance. Using a paste with a high surface area (e.g., 4.14 m 2 Pastes containing copper powders with a content of 0.1% to 0.1% PVP (PvP) or less (g) require a higher proportion of PVP, a longer hold time, and / or a higher temperature to etch the SiN coating and form a cell.

[0349] Table 15

[0350]

[0351] * Different batches of fine copper powder were used to vary the surface area of ​​the fine copper powder to produce paste 31, paste 32, and paste 33.

[0352] **In order to produce pastes with different viscosities, the amount of propylene glycol was adjusted.

[0353] Example 14. Effect of Second Oxide Particles and Nanoparticles on the Electrical Properties of the Paste

[0354] In this embodiment, the effect of the second oxide particles (e.g., Sb2O3) and the nanoparticles (e.g., Cu / Ni / Pb) on the bulk resistivity (ρ) and the contact resistivity (ρ) is described. c ). Antimony (Sb) is a known n-type dopant for silicon and is introduced as a possible n-type dopant under the contact. +region, and thus reduce the contact resistivity. In this embodiment, commercially available antimony oxide with a particle size range of 1.1μm to 1.8μm is used. Antimony oxide has a low melting point (656°C) and is located just below nickel oxide NiO on the Ellingham diagram. Therefore, it requires similar energy input to be reduced to its elemental form. In addition, its position means that antimony can reduce the oxides of other elements (Ni, Cu, Pb) in the paste, resulting in a more conductive contact. Antimony oxide is introduced into the paste using a factorial design experimental approach. In this case, the oxide is considered to be part of the glass frit system that chemically reacts with the SiN layer (in addition to the Cu / Ni / Pb nanoparticles). The amount of glass frit in the paste is kept constant, and the ratio of nanoparticles to second oxide particles is varied between 2 and 3 using predetermined "high" or "low" values ​​for the two components. 2 The paste compositions used for the designed matrix were varied. This resulted in four possible paste combinations that were mixed, screen printed on monocrystalline silicon solar cells, and fired at 690°C for 3 seconds in air (using the refractory brick method). The effects of using high and low amounts of second oxide particles in the paste on bulk resistivity, contact resistance, and device PV performance were studied. Tables 16, 17, and 18 (below) list the paste compositions used for the designed matrix.

[0355] Fig.25A , Fig.25B , Fig.25C , Fig.25D , Fig.25E and Fig.25F According to 2 2 The effect of changing the level of Cu / Ni / Pb nanoparticles and Sb2O3 particles in the paste on the bulk resistivity ρ( Fig.25A ), contact resistivity ρ c ( Fig.25B ), short circuit current density J sc ( Fig.25C ), filling factor FF( Fig.25D ), open circuit voltage V oc ( Fig.25E ) and efficiency η( Fig.25F )’s influence and interaction.

[0356] The introduction of a second oxide into the paste has a large effect in increasing both bulk and contact resistivity; and therefore has a large effect on the overall PV performance of the paste. A cross-sectional SEM image (not shown) shows improved connectivity between copper particles, but a large degree of porosity remains in the film.

[0357] Table 16

[0358]

[0359] Table 17

[0360]

[0361] Table 18

[0362]

[0363] Example 15. Second oxide particles acting as liquid sintering agent

[0364] It is desirable that the fingers have a denser microstructure to reduce the resistivity of the contacts and, therefore, the series resistance of the device. The second oxide particles (e.g., antimony oxide particles) act as a liquid sintering aid due to their relatively low melting point (656° C. for Sb2O3). A higher proportion of the second oxide particles in the paste results in a lower sintering temperature and / or a faster sintering process, as well as densification of the contacts.

[0365] Table 19 shows the composition of Paste 38, which used a 70:30 blend of coarse copper-containing particles to fine copper-containing particles (similar to the blend of Paste 5). The amount of second oxide particles was increased to about 22 wt%. Fig.26A and Fig.26B It is shown that although the copper containing particles appear to be more dense, large voids are present in the microstructure, resulting in delamination of the copper contacts from the silicon substrate. Examination of the delaminated contacts using a light box shows that the contacts still have a significant amount of porosity.

[0366] Table 19 - Paste number: Paste 38

[0367]

[0368] In order to further densify the contact without causing delamination and voids in the microstructure, the copper-containing particles need to be packed together as closely as possible and have a larger volume percentage in the contact. In order to increase the density of the contact, the spherical powder shown in Table 8 (above) of Example 11 was used to study the packing density of the copper-containing particles. It is assumed that the powder has a maximum packing factor of 0.639 and that the smaller spherical powder occupies the free space between the large copper particles for calculation. Once this value is calculated, the finest (1.2 μm to 3.2 μm) copper powder is added at 30% by weight of the copper powder in the paste. These calculations result in the following copper-containing particle blends: 37% by weight (10 μm to 22 μm), 21% by weight (7.5 μm to 14.7 μm), 12% by weight (1.8 μm to 7.7 μm), and 30% by weight (1.2 μm to 3.2 μm). Fig. 22 (d) shows an example of a cross section of a contact printed with this blend of particle sizes. Although the contact still shows a high degree of porosity, the increase in the number of inter-particle connections appears to have reduced the size of the pores.

[0369] The effect of the second oxide particles as a liquid sintering aid was studied by increasing the volume percentage of oxide particles in a paste containing a blend of four copper-containing powders having different particle sizes. The composition of the paste is shown in Table 20.

[0370] Table 20

[0371]

[0372] Fig.27A , Fig.27B and Fig.27C The effect on the microstructure of increasing the amount of second oxide particles from (a) 4.98 wt % (Paste 1) to (b) 8.49 wt % (Paste 40) and (c) 12.16 wt % (Paste 39) is shown. The larger the volume of second oxide in the contact, the denser the microstructure. However, as the copper-containing particles form a denser contact, the structure shrinks and capillary forces push the second oxide out of the narrow pores. Due to this densification and shrinkage, the print falls off the silicon substrate. The squares were placed on a light box to observe the porosity in the fired prints. Contacts printed with pastes containing 8.49 wt % and 12.16 wt % antimony oxide resulted in the inability of the contact to adhere to the silicon cell. Pools of antimony oxide (and nanoparticles) that had been reduced to their metallic form during the firing process can also be observed at the bottom of the contact, see Fig.28A and Fig.28B .

[0373] exist Fig.28A and Fig.28B , a photograph of a square printed with paste 39 is shown, wherein Fig.28A The front side of the sample is shown. Fig.28B The back side of the sample is shown. The print has come off the silicon substrate due to densification and shrinkage. The square was placed on a light box to observe the porosity in the fired print.

[0374] Example 16. Effect of Second Oxide Particles and Nanoparticles on Paste Etching Function and Firing Conditions

[0375] In this example, the contribution of the second oxide particles and the nanoparticles to the etching function of the paste is demonstrated. The total surface area contribution of the copper-containing particles used in the paste is fixed at 0.74 m 2 / g paste. The paste was printed and fired using the following settings.

[0376] The cells were fired in a semi-automatic furnace. The system consisted of a one-meter-long quartz tube with a volume of approximately 2.4 L. The furnace was constructed with a low temperature zone (Zone 1) and a high temperature zone (Zone 2) along the length of the quartz tube. Compressed air with a flow rate of 1 L / min was introduced from the starting point of Zone 1. The cells were placed on a nichrome mesh table that had been automated using stepper motors and an Arduino software program to control the speed of movement of the cells. According to (T = 38.74S -1 ), the speed S is inversely proportional to the time T required for the battery to move from zone 1 to zone 2. The set point temperatures for zone 1 and zone 2 are 150°C and 753°C, respectively. During the firing process, the battery is placed on the nichrome mesh and moved to zone 1 at a speed S, where it remains for 180 seconds. The battery is then moved to zone 2 at a speed S and remains in zone 2 for a time t 保持 The workbench was then moved back to the starting point at a speed of 32.4 cm / sec. This brought the workbench back to the starting point in less than 2 seconds. The cell was then removed from the workbench and rapidly cooled to room temperature by placing it on a metal plate.

[0377] Fig.29A , Fig.29B , Fig.29C , Fig.29D and Fig.29E The current-voltage (IV) performance of the pastes from Table 21 is shown; fired using the above method. The hold time for region 2 varies from 1 second to 5 seconds. The paste that does not contain the second oxide (Paste 9) is able to etch through the SiN layer with a hold time of less than 1 second. However, this paste etches too deeply, resulting in lower PV performance. Adding a small amount of second oxide particles (e.g., antimony oxide) to the paste (Paste 10) acts as a barrier for the nanoparticles, thereby slowing down the etching by the nanoparticles. Therefore, a hold time of 3 seconds is required before the paste etches through the SiN layer and forms a good electrical contact with the cell. Further increasing the amount of the second oxide (Paste 11, Paste 12, and Paste 13) results in a decrease in the hold time to 2 seconds. The second oxide also acts as an etchant. However, unlike the material of the nanoparticles, during the firing process, the molten material of the second oxide appears to wet and etch the SiN layer more uniformly than the material of the nanoparticles. It is believed that a smaller proportion of nanoparticles is needed to etch through the SiN coating and to allow the fingers to have a higher volume of copper. By varying the ratio of nanoparticles to second oxide particles in the paste, the firing conditions can be controlled.

[0378] Table 21

[0379]

[0380] Example 17. Effect of the Surface Area of ​​Copper-Containing Particles with Nickel on the Etching Function of the Paste and Firing Conditions

[0381] This example shows the effect of copper-containing particles on the etching and firing conditions of the paste. Table 6 shows the composition of the paste used in this example. All pastes use an antimony oxide second oxide particle to nanoparticle (Ni / Ni / Pb) ratio of 1.50. The proportion of nickel nanoparticles in the coating around the copper particles is quantified by the surface area of ​​the coated copper powder.

[0382] To vary the proportion of nickel nanoparticles in the paste, the surface area of ​​the fine copper-containing particles in the paste was varied. This was achieved by changing the surface area to 1.13 m 2 / g, 2.61m 2 / g and 25.63m 2 / g of copper powder from different batches were blended to produce a 2 Copper particles / g paste (paste 11), 0.83m 2 Copper particles / g paste (paste 14), 1.01m 2 Copper particles / g paste (paste 15) and 1.10m 2 This was achieved with a paste containing 1000 copper particles per gram of paste (Paste 16).

[0383] The samples were fired using the firing process described in Example 16. The cells were fired using Zone 2 temperatures of 753°C, 778°C, and 803°C at a table speed of 1.43 cm / sec. Table 22 (below) shows the time the cell was kept in Zone 2 to etch through the SiN layer and make contacts to produce FF>0.6. As shown, the time required increases with increasing surface area of ​​the copper-containing particles. When the highest Zone 2 temperature (i.e., 803°C) was used, the nickel particles on the copper particles no longer helped to slow the etching process and actually caused the cell to overfire.

[0384] Table 22

[0385]

[0386] Example 18. Effect of firing duration on performance during accelerated aging testing

[0387] This example shows the effect that firing conditions can have on the durability of the cell under accelerated aging conditions. The paste was used to metallize a monocrystalline silicon solar cell with an all-Al BSF back contact. The paste shown in Table 6 (Paste 15) used a total of 1.01 m 2 The cells were fired using the procedure described in Example 16 with a table speed of 1.43 cm / sec and a zone 2 temperature of 753° C. The time the cells remained in zone 2 was varied. FIG. 30F to FIG. 30HIllustrative examples of IV curves for cells held at 753°C for 4 seconds, 5 seconds, and 6 seconds are shown, respectively. The cells were thermally stressed at 200°C for up to 200 hours, and the PV performance of the device during the test is also shown in FIG. 30A to FIG. 30E Without being bound by theory, it is believed that the nanoparticles form electrical pathways across the glassy interface and also form "spikes" in the silicon surface. The results show the effect of increasing the firing duration on the battery life, where the battery exhibits improved life after firing for longer firing durations.

[0388] Example 19: Second Oxide to Nanoparticle Ratio

[0389] The second oxide particles, nanoparticles, and particles from the coated copper-containing particles in the paste form a liquid sintering aid during the firing process, causing the fingers to form denser contacts. The nanoparticles contain lead oxide / hydroxide, which lowers the melting point of the mixture when combined with other materials. When the organic material is burned out, droplets of liquid sintering aid can be discharged across the surface of the cell. These droplets can cause undesirable aesthetic defects to the cell surface. It is believed that surface defects hinder the number of photons reaching the active area of ​​the cell, thereby reducing power output. By varying the ratio of the second oxide to the nanoparticles, the amount of droplets that appear on the surface can be controlled (Figures 32(a) to (f)). In Figures 32(a) to (f), the following applies: Optical microscope images of the fingers after firing. The mass of the paste used to print the fingers is approximately 1 / 16 (4×4 cm 2 ) cell 4 mg (64 mg for a full cell). (a) The fingers were printed with a paste containing no nanoparticles (Paste 42). The fingers in the remaining images were printed with fingers containing second oxide to nanoparticle ratios of (b) 16.75 (Paste 43), (c) 8.37 (Paste 44), (d) 5.58 (Paste 45), (e) 4.19 (Paste 46), and (f) 3.35 (Paste 47). Table 23 (below) shows the composition of the pastes made without nanoparticles and at second oxide particle to nanoparticle ratios of 16.75, 8.37, 5.58, 4.19, and 3.35.

[0390] Table 23

[0391]

[0392] The amount of paste used to print the fingers directly affects the maximum second oxide particle to nanoparticle ratio that can be used; fingers using less paste can tolerate relatively small ratios before such aesthetic defects become a problem. However, using higher ratio pastes requires a higher ratio of the total amount of glass frit (i.e., second oxide and nanoparticles combined) because the second oxide is a weaker etchant than nanoparticles. As the finger width (W) size decreases (see Figure 6 ), the amount of etchant per unit area is reduced. Therefore, as the finger width decreases, the ratio can be further reduced. Example 16 (Table 21) shows a paste with a ratio of 0.50. Table 21 also shows a paste that does not contain second oxide particles and only contains nanoparticles, while Table 23 shows a paste that does not contain nanoparticles and only contains second oxide particles.

[0393] Example 20: Effect of finger size on paste composition

[0394] This example illustrates the effect of finger size on paste composition. Finger size can be reduced by reducing the number of prints, resulting in a reduction in the height of the fingers. The height and width of the fingers can also be changed by reducing the pattern size, mesh size and emulsion thickness of the screen used during the screen printing process.

[0395] Reducing the height of the fingers reduces the amount of paste on the cell. This reduces the ratio of nanoparticles and second oxide particles available per unit area. At a certain point, the amount of these materials is insufficient to etch through the anti-reflective coating. The etch rate of the combined nanoparticles and second oxide particles is reduced by the particles coated on the copper-containing particles. The more particles in the paste, the more nanoparticles and second oxide particles are needed. However, as the ratio of these materials increases, the bulk resistivity gradually increases. The amount of particles in the paste is limited by the surface area of ​​the coated copper-containing particles.

[0396] The amount of power produced by a solar cell depends on the number of photons of light that reach the cell. Therefore, the larger the area covered by the electrical conductor, the fewer photons reach the cell and the lower the power output. In order to reduce the size of the fingers, and thus reduce the amount of paste used to print the fingers without affecting the performance of the device, it is necessary to reduce the surface area of ​​the copper-containing particles per gram of paste. In order to reduce the finger width, the pattern opening size on the screen is reduced. Since the theoretical maximum particle size should be at least 2.5 times smaller than the mesh opening, it is also necessary to reduce the average particle size. Copper-containing particles have the largest particles in the paste. Therefore, reducing the particle size distribution range of this material naturally leads to an increase in the amount of coating in the paste. When the particle size range of the coarse copper-containing particles in the paste is reduced from a particle size range of 10 μm to 22 μm to 7.5 μm to 14.7 μm, the proportion of binder in the paste increases because the larger surface area makes the powder more susceptible to oxidation during the firing process. The paste is printed on a multicrystalline silicon solar cell and fired using the same semi-automatic furnace described in Example 16. Figures 33(a) and 33(b) show the effect of increasing the amount of glass frit and the surface area contribution of the copper-containing particles on the amount of paste required to maintain the fill factor of the device. In Figures 33(a) and 33(b), the following applies: Effect of increasing the amount of glass frit in the paste on PV performance (fill factor, FF) as a function of the surface area contribution used (a) 0.80 m 2 / g paste and (b)0.57m 2 / g paste as a function of the print weight of the paste made with copper-containing powder. The cells were fired using table speed = 1.43 cm / sec, zone 1 = 192°C, zone 2 = 820°C, air flow = 5 L / min, zone 2 hold time = 5 sec. The cells were 4×4 cm 2 The multicrystalline silicon cell was printed with 17 100 μm wide fingers. The composition of the paste is shown in Table 24 (below). The paste used a second oxide to nanoparticle ratio of about 16.75. The results show that by increasing the surface area contribution of the copper-containing particles from about 0.80 μm 2 / gram paste reduced to about 0.57m 2 / gram of paste, a reduction in the mass of paste required to print the fingers can be achieved. By reducing the surface area of ​​the fine copper powder in the paste from 2.41 m 2 / g is reduced to 1.61m 2 / g to control the surface area contribution of the copper-containing particles. So far, the amount of paste used to print the fingers has been controlled by the number of prints (i.e., 3 prints). The reduction in surface area results in a printing process that enables the use of a double print method to achieve devices with similar performance.

[0397] Table 24

[0398]

[0399] By reducing the surface area of ​​fine copper powder to 1.15m 2 / g, the screen printing process was reduced to a single print; thus resulting in a total surface area contribution from the copper-containing particles of 0.40 m 2 / g paste. Use 0.40m 2 / gram of paste and a second oxide to nanoparticle ratio of 16.70 to 16.75 were used to print full-size multi-Si cells. The proportion of binder in the paste was increased from 1.69 wt % to 2.32 wt %. The cells were fired in a TP Solar Model M-225 (Neutrino series) IR belt furnace. The furnace contains six heating zones and one cooling zone, which is about 30% longer than the total length of the heating section. These zones are constructed so that the front and back of the cell are heated simultaneously using IR heating lamps. The temperatures of zones 1 to 5 are 620°C, 460°C, 440°C, 450°C and 520°C, respectively. Zone 6 varies from 665°C to 690°C. The belt speed varies from 225 inches / minute to 400 inches / minute. The cells are cut into 4×4 cm 2 samples to measure PV performance. Fig.34A , Fig.34B , Fig.34C and Fig.34D The effect of firing conditions on the PV performance of diced full-size cells is shown. FIG. 34A to FIG. 34D , the following apply: PV performance ((a) short circuit current density, (b) open circuit voltage, (c) fill factor, and (d) efficiency) as a function of belt speed for firing cells in an industrial IR belt furnace. The temperatures in zones 1 to 5 of the furnace were not varied. The temperature in zone 6 was increased from 665°C to 690°C. Two versions of CuBert containing 1.69 wt% binder (Paste 54) and 2.32 wt% binder (Paste 55) were printed on full-size multicrystalline silicon cells. TM Paste. Print the battery in one print. After firing, cut the battery into 4×4cm 2 The part is measured. FIG. 34A to FIG. 34D The results in illustrate the average results for 1 / 8 to 1 / 4 full size cells. The composition of the paste is shown in Table 25.

[0400] Table 25

[0401]

[0402] The width and mass of the paste used to print the fingers can be further reduced by reducing the size of the screen openings. To achieve this, only copper-containing particles in the size range of 1.20 μm to 3.20 μm are used in the paste. Fig.35 The surface area contribution is shown to be 0.51m2 The paste was made with a copper-containing particle ratio of 3.35 and a binder concentration of 3.28 wt %. The results were for a 1 / 16 (4×4 cm 2 ) part was reduced to about 6 mg (about 96 mg for a full-size cell). The paste was printed on single crystal passivated emitter rear contact (PERC) silicon solar cells and fired using a modified version of the semi-automatic furnace described in Example 16. In this case, three separate tube furnaces were combined into a system in which a single 122 cm long quartz tube passed through all three furnaces: thus, a three-zone furnace was created. The airflow through the system was controlled by exhaust outlets located at either end of the quartz tube. The cells were placed on a nichrome wire bench that had been automated using stepper motors and an Arduino software program to control the speed at which the cells passed through the various zones. The speed at which the cells passed through the different zones was varied to simulate the belt speed used in the TP Solar IR six-zone belt furnace. The cells moved continuously through the different zones until they reached the end of the quartz tube, where a fan was turned on to quickly cool the cells back to room temperature. The cells were then removed from the bench. Fig.35 IV curves are shown for cells fired using Region 1, Region 2, and Region 3 temperatures of 255°C, 505°C, and 990°C, respectively. Fig.35 In the Figures, the following applies: Current-voltage (IV) curves of a paste made using only fine 1.2 μm to 3.2 μm copper-containing powder (Paste 56) under dark and light conditions. The paste was printed on a monocrystalline silicon PERC cell and fired using a three-zone semi-automatic furnace. The temperatures in Zone 1, Zone 2, and Zone 3 were 255°C, 505°C, and 990°C, respectively. The cell was fired at a belt speed of 325 inches / minute.

[0403] Reducing the surface area contribution of the smaller copper-containing particles 46 can further limit the belt speed at which the cell can be fired. Fig.36A , Fig.36B and Fig.36C Shown for the use of 0.51m 2 / g paste, 0.57m 2 / g paste and 0.65m 2 / g paste surface area contribution of the prepared paste and firing conditions to the open circuit voltage V of the battery oc The paste used a second oxide to nanoparticle ratio of 3.35 and a binder concentration of 3.28 wt %. The composition of the paste is shown in Table 26 (below). The lower second to nanoparticle ratio combined with the lower surface area produced a significantly lower V at slower speeds.oc .

[0404] Table 26

[0405]

[0406] The changes in paste composition, surface area contribution, and resulting paste amount required to produce devices with fill factors > 0.6 are summarized in Table 27.

[0407] Table 27

[0408]

[0409] Example 21: Controlling Etch Depth and Effect of Adhesive on Durability

[0410] Fig.37A and Fig.37B The effect of the binder ratio in the paste on the durability of the battery under accelerated aging conditions is shown. Fig.37A and Fig.37B The following applies: Accelerated aging test at 200°C for CuBert TM Effect of paste metallization on PV performance ((a) open circuit voltage, (b) pseudo fill factor) of multi-Si cells with all-Al BSF back contacts. Two versions of CuBert containing 1.69 wt% binder (Paste 54) and 2.32 wt% binder (Paste 55) were printed on 6-inch multi-Si cells. TM The results below show 4 x 4 cm cells cut from full size cells fired in an IR belt furnace using a zone 6 temperature of 665°C and a belt speed (BS) of 300 in / min. 2 The average results for the sections. The chart also shows the results for samples fired using a zone 6 temperature of 690°C and a belt speed (BS) of 325 inches / minute. Multicrystalline cells were printed using pastes containing 1.69 wt % and 2.36 wt % binder. The composition of the paste is provided in Table 25. The cells were fired using the six-zone TP Solar IR belt furnace described in Example 20. The furnace used zone 1, zone 2, zone 3, zone 4 and zone 5 temperatures of 620°C, 460°C, 440°C, 450°C and 520°C, respectively. The temperature of zone 6 varied from 665°C to 690°C. The belt speed was varied. The full size cells were cut into smaller 4×4 cm 2 The cells were then aged at 200 °C for 1000 h in an inert atmosphere. The cells were periodically pulled out throughout the test to measure their PV performance. oc The open circuit voltage V measured by the systemoc and pseudo fill factor pFF to determine performance (Figure 37). oc and pFF are sensitive to copper diffusion into the junction, and if this occurs, V oc The results show that increasing the proportion of binder in the paste reduces the depth of the paste etching into the cell, thereby increasing the durability of the cell.

[0411] Example 22: Effect of Nanoparticle Composition

[0412] The nanoparticles and the second oxide particles provide the etching function of the paste. The etching rate can be changed by changing the ratio of the two materials in the paste. It can also be changed by changing the composition of the nanoparticles. As described above, the aggressiveness of the nanoparticles can be controlled by changing the ratio of different elements during the synthesis of the nanoparticles. In this embodiment, the molar ratio of nickel (Ni) and lead (Pb) in the Ni / Ni / Pb nanoparticles is reduced from 1.52 to 0.52 during the synthesis. The paste is made using these two nanoparticle compositions and printed on a monocrystalline silicon PERC cell. The battery is fired in the three-zone semi-automatic firing system described in Example 20. The temperatures in Zone 1, Zone 2, and Zone 3 are 650°C, 450°C, and 925°C, respectively. Fig.38A and Fig.38B The effect of these nanoparticles on PV performance is shown. Fig.38A and Fig.38B In the figure, the following applies: Efficiency of monocrystalline silicon PERC solar cells printed using pastes made of standard Ni / Ni / Pb nanoparticles, where the Ni / Pb ratio is 1.52 (Paste 55 and Paste 57) and where the ratio is 0.52 (Paste 56 and Paste 58). The figure also shows the effect of doubling the ratio of nanoparticles and the amount of binder on the PV performance. The composition of the pastes is shown in Table 28.

[0413] Table 28

[0414]

[0415] Example 23: Effect of Copper-Containing Particle Size on Firing Conditions

[0416] Reducing the finger size requires not only a change in the paste composition, but also a change in the firing conditions. The smaller the size of the copper-containing particles, the easier it is for the particles to oxidize. Increasing the proportion of binder in the paste as well as the amount of etchant in the paste helps to reduce any oxides as well as those formed during firing. However, both of these components can only be increased to a certain level before affecting device performance. Therefore, the firing conditions need to be changed. The cells were fired using the three-zone semi-automatic firing system described in Example 20. In the first two zones, most of the binder was burned out, but due to the smaller finger size, the proportion of binder present was already smaller. Therefore, the temperature in the first zone was reduced to address this effect. Fig.39A , Fig.39B and Fig.39C The effect on the lateral resistance of the fingers due to the decrease in temperature in zone 1 and the increase in the amount of binder in the paste is shown. Table 29 shows the composition of the paste. The cells are 4×4 cm 2 About 3.5 mg of paste is printed on a monocrystalline silicon PERC cell. Fig.39A , Fig.39B and Fig.39C The following applies: Effect of firing conditions on the electrical resistance across 22 fingers of length 3.2 mm printed using pastes containing (a) 2.05 (Paste 59), (b) 2.35 (Paste 60), (c) 2.64 (Paste 61) wt % binder. The fingers were 4×4 cm 2 About 3.5 mg of paste is used for printing on monocrystalline silicon PERC cells.

[0417] Table 29

[0418]

[0419] Example 24: Increasing screen life of paste for smaller finger sizes

[0420] A reduction in particle size in the paste may result in a decrease in the life of the screen used for the paste because the increased surface area increases the rate at which the paste dries. Direct replacement of the solvent used in the medium with a solvent with a lower evaporation rate may extend screen life. Table 30 shows the physical properties of the solvents that have been tested in the paste.

[0421] Table 30

[0422]

[0423] Example 25: Finger Size

[0424] Table 31 shows the average size of a high viscosity paste (Paste 53) printed through a 300 mesh screen with a 20 μm emulsion over mesh (EOM) coating and 100 μm wide finger openings. The cells were fired using a TPSolar six-zone IR belt furnace with temperatures of 620°C, 460°C, 440°C, 450°C, 520°C, and 840°C for Zone 1, Zone 2, Zone 3, Zone 4, Zone 5, and Zone 6, respectively. The average width and height of the fingers were measured from cross-sectional images using optical microscopy and scanning electron microscopy, respectively, for both unfired and fired fingers. Fig.40 A cross-sectional image of the fired finger is shown. The reduction in size is due to the densification of the internal structure. A cross-sectional SEM image of a finger (printed with paste 53) fired using a TP solar six-zone IR belt furnace is shown in Fig.40 middle.

[0425] Table 31

[0426]

[0427] The printing width can be further reduced by adjusting the screen (see, for example, Figure 4 W2 in the mesh). Reducing the finger opening and increasing the mesh number to a higher number results in smaller openings, thereby reducing the amount of paste passing through the screen. Screen openings that are smaller than the target finger width are often used. In other words, the print width is usually wider than the corresponding screen opening size. Reducing the diameter of the wire in the mesh and the EOM reduces the thickness of the deposit. These changes, coupled with changes in printing speed, are common changes made to achieve the goals. Table 32 and Fig.41A and Fig.41B The effect of screen parameters on the printing width of a relatively low viscosity paste is shown. Fig.41A and Fig.41B , a 360 mesh screen with 60 μm wide finger openings (see Fig.41A ) and a 400 mesh screen with 35 μm wide finger openings (see Fig.41B ) Optical microscope image of the paste (Paste 63) after printing.

[0428] Table 32

[0429]

[0430] Although the present invention has been illustrated by describing a plurality of embodiments, and although these embodiments have been described in detail, it is not the intention of the inventors to restrict or in any way limit the scope of the appended claims to such details. Therefore, other advantages and modifications will be apparent to those of ordinary skill in the art. The various features of the present invention may be used alone or in any combination, depending on the needs and preferences of the user.

[0431] 1. A paste for metallizing a solar cell, the paste comprising:

[0432] Organic carrier, and

[0433] a mixture of copper-containing particles, metal-oxide-containing nanoparticles, and second oxide particles different from the metal-oxide-containing nanoparticles in the organic vehicle,

[0434] The second oxide particles include particles of a metal oxide, and the metal of the metal oxide is capable of reducing at least some of the metal-oxide containing nanoparticles to metal when the paste is heated to a temperature at which the organic vehicle decomposes.

[0435] 2 . The paste of claim 1 , wherein the organic vehicle is capable of reducing the metal oxide of the second oxide particles via decomposition of the organic vehicle.

[0436] 3. The paste of claim 1, wherein the organic vehicle comprises polyvinyl pyrrolidone.

[0437] The paste of claim 1 , wherein the second oxide particles comprise glass frit particles.

[0438] 5 . The paste of claim 1 , wherein the copper-containing particles comprise metallic copper particles or copper alloy particles.

[0439] 6 . The paste according to claim 5 , wherein the metallic copper particles have at least one metal of nickel, cobalt, or manganese on the surface of the metallic copper particles or on the surface of the copper alloy particles.

[0440] 7 . The paste according to claim 6 , wherein the at least one metal of nickel, cobalt or manganese is in the form of metal particles on the surface of the metallic copper particles or on the surface of the copper alloy particles.

[0441] 8. The paste of claim 6, wherein the at least one metal of nickel, cobalt or manganese is in the form of metal oxide particles on the surface of the metallic copper particles or on the surface of the copper alloy particles.

[0442] 9. The paste of claim 6, wherein the metallic copper particles or the copper alloy particles and / or the at least one metal are doped with at least phosphorus.

[0443] 10 . The paste of claim 6 , wherein surfaces of the metallic copper particles or surfaces of the copper alloy particles are not completely covered by the at least one metal.

[0444] 11. The paste of claim 6, wherein the at least one metal covers at least a portion of a surface of the metallic copper particles or covers at least a portion of a surface of the copper alloy particles.

[0445] 12. The paste of claim 1, wherein the metal oxide of the second oxide particles is antimony oxide.

[0446] 13. The paste of claim 1, wherein the metal-oxide containing nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.

[0447] 14. The paste of claim 1, wherein the metal-oxide containing nanoparticles comprise nickel oxide and lead oxide.

[0448] 15. The paste of claim 14, wherein the metal oxide of the second oxide particles comprises antimony oxide.

[0449] 16. The paste of claim 1, wherein the metal-oxide containing nanoparticles comprise nickel oxide, copper oxide, and lead oxide.

[0450] 17. The paste of claim 1, wherein the paste is free of silver.

[0451] 18. The paste of claim 1, wherein a ratio of the second oxide particles to the metal-oxide containing nanoparticles is in the range of 0.50 to 16.96 by weight.

[0452] 19. The paste of claim 1, wherein a ratio of the second oxide particles to the metal-oxide containing nanoparticles is in a range of 1.50 to 3.51 by weight.

[0453] 20. The paste of claim 1, wherein at least one metal of nickel, cobalt and manganese is in the form of metal particles on the surface of the copper-containing particles and the surface area of ​​the copper-containing particles having the metal particles is within 1 m 2 / g to 5m 2 / g range.

[0454] 21. The paste of claim 1, wherein the copper-containing particles comprise a mixture of fine copper powder and coarse copper powder.

[0455] 22. The paste of claim 21, wherein the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size in the range of 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.

[0456] 23. The paste of claim 1, wherein the organic vehicle is an organic binder and an organic solvent.

[0457] 24. The paste of claim 23, wherein the organic vehicle further comprises a viscosity modifier.

[0458] 25. The paste of claim 23, wherein the organic solvent is propylene glycol.

[0459] 26. The paste of claim 23, wherein the organic vehicle further comprises an organic binder.

[0460] 27. A paste comprising:

[0461] Organic carrier, and

[0462] a mixture of particles in the organic vehicle, the mixture of particles comprising metallic copper particles, nanoparticles and metal oxide particles,

[0463] The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

[0464] 28. The paste of claim 27, wherein the metal oxide of the metal oxide particles has a more negative Gibbs free energy of formation than the metal oxide of the at least one oxide in the nanoparticles.

[0465] 29. The paste of claim 27, wherein the metallic copper particles occupy the largest volume fraction of the metal in the paste.

[0466] 30. The paste of claim 27, wherein the nanoparticles comprise particles comprising lead oxide.

[0467] 31. The paste of claim 27, wherein the nanoparticles are nickel oxide and lead oxide.

[0468] 32. The paste of claim 27, wherein the metal oxide particles comprise particles of antimony oxide.

[0469] 33. The paste of claim 27, wherein the nanoparticles include particles comprising lead oxide and the metal oxide particles include particles of antimony oxide.

[0470] 34. The paste of claim 27, wherein the organic vehicle is capable of reducing the metal oxide particles via decomposition of the organic vehicle.

[0471] 35. The paste of claim 27, wherein the organic vehicle comprises polyvinyl pyrrolidone.

[0472] 36. The paste of claim 27, wherein the metal oxide particles comprise glass frit particles.

[0473] 37. The paste of claim 27, wherein the metallic copper particles have at least one metal of nickel, cobalt, or manganese on the surface of the metallic copper particles.

[0474] 38. The paste of claim 37, wherein the at least one metal of nickel, cobalt or manganese is in the form of metallic particles on the surface of the metallic copper particles.

[0475] 39. The paste of claim 37, wherein the at least one metal of nickel, cobalt or manganese is in the form of metal oxide particles on the surface of the metallic copper particles.

[0476] 40. The paste of claim 37, wherein the metallic copper particles and / or the at least one metal are doped with at least phosphorus.

[0477] 41. The paste of claim 37, wherein surfaces of the metallic copper particles are not completely covered by the at least one metal.

[0478] 42. The paste of claim 37, wherein the at least one metal covers at least a portion of a surface of the metallic copper particles.

[0479] 43. The paste of claim 37, wherein the metal oxide particles are particles of antimony oxide.

[0480] 44. The paste of claim 37, wherein the nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.

[0481] 45. The paste of claim 37, wherein the nanoparticles comprise nickel oxide and lead oxide.

[0482] 46. ​​The paste of claim 45, wherein the metal oxide particles are particles of antimony oxide.

[0483] 47. The paste of claim 37, wherein the nanoparticles comprise nickel oxide, copper oxide, and lead oxide.

[0484] 48. The paste of claim 27, wherein the paste is free of silver.

[0485] 49. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 0.5 to 17 by weight.

[0486] 50. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 1.5 to 3.5 by weight.

[0487] 51. The paste of claim 27, wherein the metallic copper particles are modified to include metal-containing particles on the surface of the metallic copper particles.

[0488] 52. The paste of claim 51, wherein the surface area of ​​the modified metallic copper particles is greater than the surface area of ​​the unmodified metallic copper particles.

[0489] 53. The paste of claim 51, wherein the surface area of ​​the modified metallic copper particles is 1 m 2 / g to 5m 2 / g range.

[0490] 54. The paste of claim 27, wherein the metallic copper particles comprise a mixture of fine copper powder and coarse copper powder.

[0491] 55. The paste of claim 54, wherein the fine copper powder is characterized by an average particle size in a range of 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size in a range of 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.

[0492] 56. The paste of claim 27, wherein the organic vehicle is an organic binder and an organic solvent.

[0493] 57. The paste of claim 56, wherein the organic vehicle further comprises a viscosity modifier.

[0494] 58. The paste of claim 56, wherein the organic solvent is propylene glycol.

[0495] 59. The paste of claim 56, wherein the organic vehicle further comprises an organic binder.

[0496] 60. A paste consisting essentially of:

[0497] Organic carrier, and

[0498] a mixture of metallic copper particles, nanoparticles and metal oxide particles in the organic carrier,

[0499] The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

[0500] 61. A paste consisting of:

[0501] Organic carrier, and

[0502] a mixture of metallic copper particles, nanoparticles and metal oxide particles in the organic carrier,

[0503] The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

[0504] 62. A solar cell comprising:

[0505] a semiconductor substrate; and

[0506] at least one copper-containing conductor on said semiconductor substrate,

[0507] The copper-containing conductor includes a plurality of grains of copper or a copper alloy, and at least a portion of grain boundaries between adjacent grains contain at least one of lead, copper, cobalt, manganese, tellurium and bismuth and at least one other metal.

[0508] 63. The solar cell of claim 62, wherein the oxide of at least one other metal has a more negative Gibbs free energy of formation than lead oxide.

[0509] 64. The solar cell of claim 62, wherein the at least one other metal is antimony.

[0510] 65. The solar cell of claim 62, wherein at least a portion of the grain boundaries further comprise nickel.

[0511] 66. The solar cell of claim 62, wherein the copper-containing conductor and the semiconductor substrate meet at an interface, and the interface comprises lead and the at least one other metal between the semiconductor substrate and the grains.

[0512] 67. The solar cell of claim 66, wherein the interface comprises a metal silicide.

[0513] 68. The solar cell of claim 66, wherein the interface further comprises nickel.

[0514] 69. The solar cell of claim 62, wherein the solar cell is free of silver.

[0515] 70. The solar cell of claim 62, wherein the copper-containing conductor is a finger.

[0516] 71. The solar cell of claim 70, wherein the fingers have a thickness in the range of 10 μm to 100 μm.

[0517] 72. The solar cell of claim 70, wherein the solar cell comprises a highly doped silicon emitter layer, and the fingers are in electrical contact with the silicon emitter layer.

[0518] 73. The solar cell of claim 70, wherein the resistivity of the fingers is in the range of 2 to 10 times the resistivity of bulk metallic copper.

[0519] 74. The solar cell of claim 62, wherein the conductor is a bus bar.

[0520] 75. The solar cell of claim 74, wherein the busbar has a thickness in the range of 10 μm to 100 μm.

[0521] 76. The solar cell of claim 74, wherein the solar cell comprises an anti-reflection layer on the semiconductor substrate, the anti-reflection layer defining an outer surface of the solar cell, and the bus bar is in direct contact with the anti-reflection layer but not with the semiconductor substrate.

[0522] 77. The solar cell of claim 62, wherein the solar cell further comprises a plurality of bus bars arranged in a pattern wherein the bus bars are spaced apart at a distance less than 40 mm.

[0523] 78. The solar cell of claim 62, wherein said solar cell is devoid of a separately deposited diffusion barrier layer between said copper conductor and said semiconductor substrate.

[0524] 79. A method of manufacturing a solar cell, comprising:

[0525] A paste is placed on the surface of the substrate, the paste comprising:

[0526] Organic carrier, and

[0527] a mixture of particles in the organic vehicle, the mixture of particles comprising metallic copper particles, nanoparticles and metal oxide particles,

[0528] wherein the nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide; and

[0529] The paste is heated to a temperature at which the organic vehicle decomposes and reduces at least some of the metal oxide to metal.

[0530] 80. The method of claim 79, wherein heating comprises heating in air.

[0531] 81. The method of claim 79, wherein during heating, the metal reduces at least some of the metal-oxide containing nanoparticles to metal.

[0532] 82. The method of claim 81, wherein the substrate comprises a silicon nitride layer, and during heating, the heated metal oxide and metal react with the silicon nitride layer.

[0533] 83. A method for modifying the surface of copper-containing particles for paste, the method comprising:

[0534] mixing copper-containing particles with metal ions in a solution;

[0535] adding a reducing agent to the mixture of copper-containing particles and metal ions to reduce the metal ions to metals, so that the metals are deposited on the surfaces of the copper-containing particles; and

[0536] Surface modified copper-containing particles are separated from the solution.

[0537] 84. The method of claim 83, further comprising:

[0538] A mixture containing copper particles, metal ions and a reducing agent is heated.

[0539] 85. The method of claim 83, wherein the surface modified copper-containing particles have a surface area greater than the copper particles prior to depositing the metal.

[0540] 86. The method of claim 83, wherein the surface modified copper-containing particles have a surface area of ​​at least 0.83 m 2 / g.

[0541] 87. The method of claim 83, wherein the metal ion is one or more of nickel, manganese, and cobalt.

[0542] 88. A paste comprising the surface modified copper-containing particles of claim 83.

[0543] 89. A method of preparing a paste for metallizing a solar cell, comprising:

[0544] A plurality of particles are mixed together in an organic vehicle, wherein the plurality of particles include copper-containing particles, nanoparticles, and second oxide particles.

[0545] 90. The method of claim 89, wherein prior to mixing, the method further comprises:

[0546] The surface of the copper-containing particles is modified to increase the surface area of ​​the copper-containing particles by 1.5% to 20%.

[0547] 91. The method of claim 89, wherein prior to mixing, the method further comprises:

[0548] The surface of the copper-containing particles is modified by exposing the copper-containing particles to a solution and depositing particles of metal and / or metal oxide on the surface of the copper-containing particles.

[0549] 92. The method of claim 89, wherein prior to mixing, the method further comprises:

[0550] A first powder comprising the copper-containing particles is mixed with a second powder comprising the copper-containing particles, the first powder being characterized by a first average particle size and a first particle size distribution, and the second powder being characterized by a second average particle size and a second particle size distribution, the first average particle size being greater than the second average particle size.

[0551] 93. The method of claim 89, wherein mixing comprises mixing at least 80 weight percent of the copper-containing particles, 1 weight percent to 15 weight percent of the second oxide particles, and 1 weight percent to 10 weight percent of the nanoparticles with 1 weight percent to 13 weight percent of an organic vehicle.

[0552] 94. The method of claim 89, wherein mixing comprises mixing together metallic copper particles, nanoparticles comprising at least lead, and antimony oxide particles.

[0553] 95. The paste of claim 1, wherein the copper-containing particles consist of fine copper powder.

[0554] 96. The paste of claim 95, wherein the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm.

[0555] 97. The paste of claim 1, wherein a ratio of second oxide particles to metal-oxide containing nanoparticles is in the range of 0.25 to 20 by weight.

[0556] 98. The paste of claim 1, wherein the ratio of second oxide particles to metal-oxide containing nanoparticles is in the range of 3 to 17 by weight.

[0557] 99. The paste of claim 1, wherein at least one metal of nickel, cobalt and manganese is in the form of metal particles on the surface of the copper-containing particles and the surface area of ​​the copper-containing particles having metal particles is within 0.7 m 2 / g to 5m 2 / g range.

[0558] 100. The paste of claim 27, wherein the nanoparticles comprise particles comprising lead hydroxide and the metal oxide particles comprise particles of antimony oxide.

[0559] 101. The paste of claim 56, wherein the organic solvent is one or a combination of propylene glycol, dipropylene glycol, and tripropylene glycol.

[0560] 102. The method of claim 83, wherein the surface modified copper-containing particles have a surface area of ​​at least 0.66 m 2 / g.

[0561] 103. The method of claim 89, wherein prior to mixing, the method further comprises:

[0562] The surface of the copper-containing particles is modified to increase the surface area of ​​the copper-containing particles by at least 1.5%.

[0563] 104. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 0.25 to 20 by weight.

[0564] 105. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 3 to 17 by weight.

[0565] 106. The paste of claim 51, wherein the surface area of ​​the modified metallic copper particles is between 0.7 m 2 / g to 5m 2 / g range.

[0566] 107. The paste of claim 27, wherein the metallic copper particles consist of fine copper powder.

[0567] 108. The paste of claim 107, wherein the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm.

[0568] 109. The paste of claim 33, wherein the nanoparticles further comprise particles comprising lead hydroxide.

Claims

1. A paste for metallizing a solar cell, the paste comprising: Organic carrier, and a mixture of copper-containing particles, metal-oxide-containing nanoparticles, and second oxide particles different from the metal-oxide-containing nanoparticles in the organic vehicle, The second oxide particles include particles of a metal oxide, and the metal of the metal oxide is capable of reducing at least some of the metal-oxide containing nanoparticles to metal when the paste is heated to a temperature at which the organic vehicle decomposes.

2. A paste comprising: Organic carrier, and a mixture of particles in the organic vehicle, the mixture of particles comprising metallic copper particles, nanoparticles and metal oxide particles, The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

3. A paste consisting essentially of: Organic carrier, and a mixture of metallic copper particles, nanoparticles and metal oxide particles in the organic carrier, The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

4. A paste consisting of: Organic carrier, and a mixture of metallic copper particles, nanoparticles and metal oxide particles in the organic carrier, The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide and lead oxide.

5. A solar cell comprising: Semiconductor substrate; and at least one copper-containing conductor on said semiconductor substrate, The copper-containing conductor includes a plurality of grains of copper or a copper alloy, and at least a portion of grain boundaries between adjacent grains contain at least one of lead, copper, cobalt, manganese, tellurium and bismuth and at least one other metal.

6. A method for manufacturing a solar cell, comprising: A paste is placed on the surface of the substrate, the paste comprising: Organic carrier, and a mixture of particles in the organic vehicle, the mixture of particles comprising metallic copper particles, nanoparticles and metal oxide particles, wherein the nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide; and The paste is heated to a temperature at which the organic vehicle decomposes and reduces at least some of the metal oxide to metal.

7. A method for modifying the surface of copper-containing particles for paste, the method comprising: mixing copper-containing particles with metal ions in a solution; adding a reducing agent to the mixture of copper-containing particles and metal ions to reduce the metal ions to metals, so that the metals are deposited on the surfaces of the copper-containing particles; and Surface modified copper-containing particles are separated from the solution.

8. A paste comprising the surface modified copper-containing particles of claim 7.

9. A method for preparing a paste for metallizing a solar cell, comprising: A plurality of particles are mixed together in an organic vehicle, wherein the plurality of particles include copper-containing particles, nanoparticles, and second oxide particles.

10. The method of claim 9, wherein before mixing, the method further comprises: The surface of the copper-containing particles is modified to increase the surface area of ​​the copper-containing particles by 1.5% to 20%.

Citation Information

Cited By

  • Solar cell and photovoltaic module

    CN120456662A

  • Solar cells and photovoltaic modules

    CN120456662B